System and method for mitigating thermal propagation in battery-based energy storage system
Compressible thermal barriers with multilayer materials mitigate thermal runaway in lithium-ion batteries by preventing heat transfer and maintaining energy density, ensuring safety and performance.
Patent Information
- Application Number
- JP2024187363
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-28
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing lithium-ion batteries are susceptible to thermal runaway events due to rapid self-heating, which can lead to catastrophic failures such as fires or explosions, and current mitigation methods either limit energy density or are not effective in preventing heat propagation during thermal events.
The implementation of compressible thermal barriers, including multilayer materials with insulating, thermally conductive, and sacrificial layers, to prevent heat transfer between adjacent cells during thermal events, maintaining optimal temperature and structural integrity while accommodating cell expansion.
The compressible thermal barriers effectively shield adjacent cells from thermal runaway, minimizing heat propagation and maintaining energy density, while providing mechanical resilience and fire resistance, thus enhancing safety and performance of lithium-ion batteries.
Smart Images

Figure 2025010194000002 
Figure 2025010194000003 
Figure 2025010194000004
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Patent Application No. 63 / 218,205, filed on July 2, 2021, and entitled "Materials, Systems, and Methods for Mitigation of Electrical Energy Storage Thermal Events," U.S. Provisional Patent Application No. 63 / 324,060, filed on March 26, 2022, and entitled "Systems and Methods for Mitigating Thermal Propagation in Battery-Based Energy Storage Systems," and U.S. Provisional Patent Application No. 63 / 324,522, filed on March 28, 2022, and entitled "Systems and Methods for Mitigating Thermal Propagation in Battery-Based Energy Storage Systems," each of which is incorporated by reference in its entirety into this specification.
[0002] The present disclosure generally relates to systems and methods for mitigating thermal events, such as thermal runaway problems, in energy storage systems. In particular, the present disclosure provides systems, methods, and techniques for preventing thermal propagation from occurring in adjacent cells, modules, or packs after a portion of a battery-based energy storage system experiences a thermal event (e.g., thermal runaway). The present disclosure further relates to battery modules or battery packs having one or more battery cells that include an amount (e.g., thickness, volume, etc.) of thermal barrier material according to the present technology to mitigate thermal propagation, as well as systems including those battery modules or battery packs. [Background technology]
[0003] Rechargeable batteries, such as lithium-ion batteries, have found wide applications in motor-driven energy storage systems. Lithium-ion batteries (LIBs) are widely used in powering portable electronic devices, such as cell phones, tablets, laptops, power tools, and other high current devices, such as electric vehicles, due to their high operating voltage, low memory effect, and high energy density compared to conventional batteries. However, there are safety concerns because LIBs are susceptible to catastrophic failure under "severe conditions," such as when rechargeable batteries are overcharged (charged beyond their design voltage), overdischarged, operated at high temperatures and pressures, or exposed to high temperatures and pressures. As a result, the narrow operating temperature range and charge / discharge rates limit the use of LIBs, as they may fail due to rapid self-heating or thermal runaway events when exposed to conditions outside their design range.
[0004] As shown in Figure 1, the electrochemical cell of a LIB mainly consists of a positive electrode, a negative electrode, an electrolyte capable of conducting lithium ions, a separator separating the positive electrode and the negative electrode, and a current collector. 0.8 Co 0.15 Al 0.05 O2(NCA), and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2 (NMC), are the six types of cathode materials widely used in Li-ion batteries. These six types of batteries account for the majority of the market share in the current battery market. The electrolyte consists of lithium salts dissolved in a specific solvent (mainly including ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and propylene carbonate (PC)). The lithium salts are generally selected from LiClO4, LiPF6, LiBF4, LiBOB, etc. The separator material is generally a polyolefin-based resin material. Microporous membranes of polypropylene (PP) and polyethylene (PE) are usually used as separators in commercial lithium-ion batteries. Aluminum foil is usually used as the current collector for the positive electrode and copper foil for the negative electrode. Carbon-based materials, including hard carbon, carbon nanotubes, and graphene, are currently the primary choice for the negative electrode in most commercial lithium-ion batteries. Other novel negative electrode materials, such as titanium-based oxides, alloy / de-alloyed materials, and conversion materials, are also being investigated, which have shown good thermal and electrochemical performance.
[0005] LIB operation under normal conditions In normal operation, lithium ions move by diffusion and migration from one electrode to the other through the electrolyte and separator.
[0006] Charging a LIB causes lithium ions in the electrolyte solution to migrate from the cathode through the separator and into the anode where they insert themselves (Figure 2). Charge-balancing electrons also move to the anode but through the external circuit of the charger. When discharging, a reverse flow process occurs and electrons flow through the device being powered (Figure 2). During this process, heat is generated in the cell by three main mechanisms. The first mechanism is reversible heat caused by the entropic changes associated with the redox reactions that occur during the lithiation process (discharging) and delithiation process (charging process). Reversible heat is also called entropic heat. The second mechanism is irreversible heat associated with electrode polarization caused by cell overvoltage. Finally, there is irreversible heat associated with resistive losses, which is called Joule heating. Joule heating is due to the movement of lithium ions and electrons in the cell. Under normal conditions, self-heating is very small, generally of minor importance, and can be easily dissipated by good battery design or battery thermal management systems. However, under extreme conditions, several side reactions can occur that lead to thermal runaway. Understanding the causes of thermal runaway can guide the design of functional materials to improve the safety and reliability of LIBs.
[0007] Overview of thermal runaway and thermal runaway propagation Thermal runaway can occur when the internal reaction rate increases to the point where more heat is generated than can be extracted, resulting in a further increase in both reaction rate and heat generation. During thermal runaway, high temperatures trigger a chain of exothermic reactions in the battery, causing the temperature of the battery to rise rapidly. In many cases, when thermal runaway occurs in one battery cell, the generated heat causes cells in close proximity to the cell experiencing thermal runaway to heat up faster. Each cell that adds to the thermal runaway reaction traps additional energy to continue the reaction, causing thermal runaway propagation within the battery pack (Figure 3), ultimately resulting in a catastrophic accident resulting in fire or explosion. Rapid heat dissipation and effective blocking of the heat transfer path can be an effective measure to reduce the danger caused by thermal runaway propagation.
[0008] Thermal runaway induction - harsh conditions Thermal runaway can be induced by various types of runaway including mechanical runaway, electrical runaway, and thermal runaway (Figure 3). Each type of runaway can induce an internal short circuit (ISC) in the battery resulting in an increase in temperature. The harsh conditions can be externally or internally initiated. For example, service induced stress, degradation, design errors, construction parameters such as cell spacing, cell interconnection style, cell form factor, manufacturing, operation, and maintenance are internal factors that can cause various types of runaway. External factors include damage or injury to the LIB, such as from dropping the cell or from a cell being pierced.
[0009] Machine runaway Mechanical runaway is mainly caused by mechanical forces and usually occurs due to external factors such as severe car accidents, including impact, crushing, penetration, and bending. When a battery or battery pack is impacted or caught in a collision, potential damage inside the battery can occur, including separator rupture and flammable electrolyte leakage, initiating ISC and then thermal runaway. Destructive deformation and displacement caused by applied forces are two common characteristics of mechanical runaway. Battery pack deformation is quite possible during a car crash. The layout of the battery pack installed in an electric vehicle affects the crash response of the battery pack. Battery pack deformation can have dangerous effects. Battery separators can be torn, causing an internal short circuit (ISC). Flammable electrolyte leaks, potentially resulting in a fire. Penetration is another common phenomenon that can occur during a vehicle crash. Comparing with the crushing condition, when penetration is initiated, violent ISC can be instantly triggered. Mechanical breakdown and electrical shorting can occur simultaneously, making the intrusion severity even more severe than simple mechanical or electrical runaway.
[0010] Electrical Runaway Electrical runaway mainly includes internal or external short circuit, overcharging, and over-discharging of the LIB.
[0011] Internal short circuits occur in over 90% of severe conditions. Roughly speaking, an internal short circuit occurs when the battery separator fails, causing the cathode and anode to collide with each other. Internal short circuits can be caused by (1) mechanical runaway, when the separator fails by penetration or crushing, (2) electrical runaway, when the separator penetrates due to dendritic growth (Figure 4), and (3) thermal runaway, when the separator collapses at high temperatures.
[0012] When electrodes with a voltage difference are connected by a conductor, an external short circuit is formed. An external short circuit in a battery pack can be caused by deformation during a car crash, water ingress, contamination by a conductor, or electric shock during maintenance. Compared to intrusion, the heat released on the circuit of an external short circuit generally does not heat the cell. An external short circuit can cause large current and high heat generation in the battery, which is mainly caused by heat generation according to Ohm's law. When the temperature starts to exceed about 70°C, the cell starts to break. As a result, it can induce discharge and electrolyte leakage.
[0013] Overcharging can be defined as charging a battery beyond its design voltage. Overcharging can be induced by the inherent high current density, vigorous charging profile, etc., which can cause a series of problems including the deposition of Li metal on the anode and severely affect the electrochemical performance and safety of the battery, the decomposition of the cathode material releasing oxygen, and the decomposition of the organic electrolyte releasing heat and gaseous products (H2, hydrocarbons, CO, etc.). The overcharging process can be divided into three stages. In the first stage, (1) the voltage and temperature remain unaffected and essentially unchanged; in the second stage, (2) lithium dendrite deposition occurs on the voltage platform; and in the third stage, (3) heat and gas are generated, causing the voltage to drop dramatically and thermal runaway to occur in the battery.
[0014] Over-discharge is another possible electrical harsh condition. Generally, the voltage mismatch of multiple cells in a battery pack is inevitable. Therefore, when the battery management system cannot monitor the voltage of any single cell, the cell with the lowest voltage will be over-discharged. The mechanism of over-discharge runaway is different from other mechanisms, and the potential danger can be underestimated. The cell with the lowest voltage in the battery pack can be forced to discharge by other cells connected in series during over-discharge. During the forced discharge, the polarity is reversed and the cell voltage becomes negative, resulting in abnormal heating in the over-discharged cell.
[0015] thermal runaway Thermal runaway is generally triggered by overheating. Overheating of lithium-ion batteries can occur due to mechanical runaway, electrical runaway, and loss of contact in connectors. Generally, at normal operating temperatures, LIBs are stable. However, above a certain temperature, the stability of LIBs becomes unpredictable, and at elevated temperatures, chemical reactions within the battery case produce gases that lead to an increase in internal pressure within the battery case. These gases can further react with the cathode, releasing more heat and creating temperatures within or adjacent to the battery that can ignite the electrolyte in the presence of oxygen. When the electrolyte burns, oxygen is produced, further intensifying the combustion. At some point, the increase in pressure within the battery case leads to the rupture of the battery case. The escaping gases can ignite and burn.
[0016] Thermal runaway caused by mechanical, electrical and thermal harsh conditions can induce continuous heat generation, resulting in an increase in temperature inside the battery. A series of chain reactions can occur at different stages as the temperature increases. Thermal runaway follows a mechanism of chain reactions, such as physical and / or chemical processes, during which decomposition reactions of battery component materials occur one after another (FIG. 3).
[0017] Overview of the chain reaction during thermal runaway Understanding the evolution of these physical and / or chemical processes helps develop mitigation measures for thermal runaway in LIBs. LIBs may have different inducements for thermal runaway in different temperature states or regimes, including State I: low temperature (<0°C), State II: normal temperature (0-90°C), and State III: high temperature (>90°C) (Figure 5).
[0018] In state I, LIBs cannot operate efficiently because low temperatures result in a slowdown in the electrochemical reaction rate. At low temperatures, battery performance drops dramatically as a result of the activity of the electrode materials and the slowdown in the lithium ion diffusion rate in the electrolyte. The consequences of the slowdown in chemical reactions at low temperatures include unwanted Li deposition, plating, and dendrite growth. Dendrites are tree-like structures that can form on the lithium plating of the battery. Dendrites can quickly penetrate the battery separator and the porous plastic membrane between the battery anode and cathode (Figure 4). Li deposition and dendrite growth in the cell are considered to be the main factors for inducing thermal runaway at low temperatures. Without wishing to be bound by theory, it is believed that unwanted Li deposition and dendrites can cause ISC in the battery, resulting in thermal runaway.
[0019] In state II (normal temperature operation), heat generation is minimal compared to the heat generated in the thermal runaway process. Heat generation during this operating state is mainly caused by Li-ion diffusion in the solid and liquid phases, electrochemical reactions at the solid-liquid interface, and side reactions. Heat generation can cause temperature rise and temperature differences inside the battery, and these temperature differences can affect the life and safety of the lithium-ion battery. During state II, incipient overheating can occur as a result of at least one of the internal or external inducements mentioned above, such as the battery being overcharged, exposure to excessive temperature, external short circuit due to miswiring, or internal short circuit due to cell defects. When incipient overheating begins, the battery operation changes from normal to abnormal as the temperature increases toward 90°C. When the temperature increases above 40°C, the life of the lithium-ion battery can be shortened due to faster side reactions, and when the temperature increases to about 90°C or higher, it can induce the decomposition of the solid electrolyte interphase interface (SEI) film, which is defined as the onset of thermal runaway. The SEI is formed on the anode of a lithium-ion battery during the first few charging cycles. The SEI provides a passivation layer on the anode surface that prevents further electrolyte decomposition, resulting in the long calendar life required for many applications. The initial decomposition of the SEI is considered as the first side reaction that occurs during the entire process of thermal runaway. The initial decomposition of the SEI occurs at 80-120°C, with a peak at about 100°C. The onset temperature can be lower than 80°C, as reported by Wang et al. (Thermochim.Acta 437(2005)12-16) who reported that the decomposition of the SEI can start from temperatures as low as 57°C.
[0020] Decomposition of SEI When stage III begins, the internal temperature rises rapidly, resulting in the decomposition of the SEI film. The SEI layer mainly consists of stable components (such as LiF and Li2CO3) and metastable components (such as polymers, ROCO2Li, (CH2OCO2Li)2, and ROLi). However, the metastable components can exothermically decompose at temperatures above about 90°C, releasing flammable gases and oxygen. The decomposition of the SEI film is believed to initiate thermal runaway, which then triggers a series of exothermic reactions.
[0021] When decomposition of the SEI occurs, the temperature rises and the lithium metal or intercalated lithium in the anode reacts with the organic solvent in the electrolyte, releasing flammable hydrocarbon gases (ethane, methane, etc.), an exothermic reaction that further energizes the temperature rise.
[0022] Disassembly of the separator When T (temperature) > approx. 130°C, the polyethylene (PE) / polypropylene (PP) separator begins to melt, further worsening the situation and causing a short circuit between the cathode and anode. The melting of the PE / PP separator is a thermal adsorption process, but the ISC caused by the melting of the separator further exacerbates the thermal runaway process.
[0023] Gas evolution and decomposition of electrolytes When T (temperature) > approx. 180°C, the heat generated by the ISC causes the decomposition of the lithium metal oxide cathode material, resulting in the release of oxygen. The failure of the cathode also generates higher heat, which further increases the temperature and pressure, resulting in further accelerated reactions. The heat accumulation and gas release (oxygen and combustible gases) can then induce the combustion and explosion of the lithium-ion battery.
[0024] In the thermal runaway process, only 2% of the heat is generated by the ISC, and 98% is generated by chemical reactions, including the decomposition of the SEI layer, the decomposition of the electrolyte, etc. The largest proportion of heat generated by the rapid redox reaction between the cathode and the anode is about 48%, while the heat generated by other chemical reactions in the anode, cathode, and electrolyte is much smaller. The smallest heat is generated by the decomposition of the SEI film.
[0025] The need for mitigation measures against thermal runaway Based on the understanding of the mechanisms that lead to battery thermal runaway, many approaches have been explored with the goal of reducing safety hazards through rational design of battery components. To prevent such cascading thermal runaway events from occurring, LIBs are typically designed to either keep the stored energy low enough, or to utilize sufficient insulating material between cells inside a battery module or pack, or to insulate cells from thermal events that may occur in adjacent cells, or a combination of both. The former severely limits the amount of energy that can potentially be stored in such devices. The latter limits the effective energy density by restricting the manner in which closed cells can be installed. Effective insulation and heat dissipation measures are needed to mitigate the possibility of thermal runaway in LIBs.
[0026] Current heat dissipation methods used for LIBs Currently, several different means are utilized to maximize energy density while taking precautions to prevent cascading thermal runaway. One approach is to incorporate a sufficient amount of insulation between cells or clusters of cells. This approach is generally considered desirable for safety benefits. However, with this approach, the ability of the insulating material to contain heat combined with the volume of insulation required dictates an upper limit on the energy density that can be achieved. Another approach is through the use of phase change materials. These materials undergo an endothermic phase change when a certain elevated temperature is reached. The endothermic phase change absorbs some of the heat being generated, thus cooling the localized area. Generally, for electrical storage devices, these phase change materials rely on hydrocarbon materials such as waxes and fatty acids. Although these systems are effective at cooling, they are themselves flammable and thus are not beneficial in preventing thermal runaway if an ignition occurs within the storage device. The incorporation of an intumescent material is another measure to prevent cascading thermal runaway. These materials expand above a specified temperature and produce a char designed to be lightweight and provide thermal insulation when needed. While these materials can be effective in providing insulating benefits, the expansion of the material must be considered in the design of the storage device.
[0027] The need for novel thermal barriers to meet the mechanical demands of LIB systems The expansion of the anode and cathode during charging and discharging can result in dimensional (swelling) changes of the cell. For example, silicon undergoes typical volume changes of up to 300% during intercalation, while graphite undergoes volume expansion of about 10%. This change results in both reversible and irreversible components, with the magnitude depending on the exact cell chemistry. Reversible changes in cell thickness depend only on the cell's state of charge (SOC) and can result in thickness increases of more than 2%. Irreversible expansion of the cell is associated with an increase in pressure inside the cell and is caused by the formation of the SEI. The largest contributor to this change occurs during the first charging cycle, when the SEI is first formed, but the expansion continues during the life of the cell.
[0028] Although extensive research has been conducted to create new materials that possess favorable thermal properties to prevent thermal runaway problems, the mechanical properties of those materials have not received much attention, despite their importance. For example, there is a need for an effective thermal barrier used between cells in a battery module or battery pack that can provide resistance to compressive deformation to accommodate the continued expansion of the cells during the life of the cells. In addition, during the initial assembly of the battery module, relatively low loads of 1 MPa or less are typically applied to the materials between the cells. When the cells inside the battery module or battery pack expand or swell during charge / discharge cycles, loads of up to about 5 MPa can be applied to the materials between the cells. Thus, the compressibility, compressive elasticity, and compliance of the material, e.g., the thermal barrier between the cells, are important properties.
[0029] Therefore, novel thermal barriers that meet the mechanical requirements of LIB systems are needed to provide effective insulation under thermal runaway conditions and effective heat dissipation under normal conditions. Summary of the Invention
[0030] It is an object of the present disclosure to obviate or reduce at least one of the disadvantages of the above-mentioned prior methods and systems for preventing or mitigating thermal propagation in a rechargeable battery system, such as a lithium-ion battery. The present disclosure provides methods and systems that include a compressible thermal barrier. The compressible thermal barrier of the present disclosure is sized to prevent thermal propagation between adjacent cells, modules, and / or packs when a portion of an energy source experiences a thermal event.
[0031] In the context of this disclosure, mitigated heat propagation means that cells adjacent to a damaged cell (i.e., a cell that has experienced a thermal event that exceeds a critical temperature) do not experience thermal runaway. That is, the cells adjacent to the damaged cell are shielded from the heat dissipated from the damaged cell. Thanks to this shielding or barrier, the temperature in the adjacent cells does not exceed the critical temperature, and therefore the cells adjacent to the damaged cell are not forced into thermal runaway.
[0032] In particular, it is an object of the present disclosure to provide methods and systems for mitigating heat propagation using thermal barrier materials of a predetermined size. These methods and systems are based on an understanding of the areal energy density of an individual cell (i.e., the energy stored in the cell over the area available for energy transfer to adjacent cells). The predetermined size (e.g., thickness) is adjusted to meet the areal energy density requirements of the cells. In some embodiments, the predetermined thickness prevents heat propagation from a thermally damaged cell from reaching any adjacent cells. In some embodiments, the predetermined thickness is selected such that its compressed thickness (i.e., compressed thickness between two adjacent cells during operation) prevents heat propagation from the damaged cell to adjacent cells. Typically, the compressible thermal barrier provides this heat propagation protection for an extended period of time, for example, for the entire period that the damaged cell is compromised (i.e., during the entire burn event of the damaged cell). In some embodiments, the thickness of the compressible thermal barrier is selected to provide protection for a specific period of time, for example, 25 minutes, 30 minutes, 1 hour, 2 hours, 3 hours, 5 hours, 24 hours. In certain embodiments, the compressible thermal barrier disposed between adjacent cells / modules / packs, etc., has a predetermined size (e.g., thickness) in the uncompressed state ranging from 1.5 mm to about 7 mm. In some embodiments, the compressible thermal barrier disposed between adjacent cells / modules / packs, etc., has a predetermined size (e.g., thickness) in the uncompressed state ranging from 2 mm to about 6 mm. When compressed, the compressible thermal barrier has a reduced thickness compared to the uncompressed state. A typical compressed thickness is in the range of about 0.8 mm to 6 mm. In some embodiments, the compressed thickness is about 1.0 mm, about 1.25 mm, about 1.5 mm, about 1.75 mm, or about 2.0 mm.
[0033] Another object of the present disclosure is to provide a battery module or battery pack using the system and method according to the present disclosure, which can protect the battery pack from thermal damage caused by thermal runaway of one cell and ensure a safe design of the battery pack.
[0034] In one general aspect, the present disclosure aims to provide a battery module and a battery pack that are used to simultaneously improve the heat dissipation performance and the thermal runaway protection performance of a power battery. Referring to FIG. 6, in a powered energy storage system, it is common for several cells 100 to be packed together in a preselected configuration (e.g., in parallel, in series, or in combination) to form a battery module 200. Several such battery modules can be further combined or joined to form various battery packs 300 as known in the art. During operation and discharge, such cells, battery modules, or battery packs usually generate or generate a quantity of heat that can significantly adversely affect the performance resulting therefrom. Therefore, in order to maintain a desired or optimal performance by such cells, or the resulting battery module or battery pack, it is generally important to maintain the temperature of such cells, battery modules, or battery packs within a fairly narrow prescribed range. The goal of the present disclosure is to maintain the temperature of such cells, battery modules, or battery packs within an optimal range.
[0035] In addition to maintaining the temperature of the cell within a specified range, there is also a goal to maintain the structural integrity of the cell. The materials within the cell need to be both flexible and resilient to accommodate changes in volume during operation of the battery. In some embodiments, the methods and systems include flame retardant or fire resistant materials incorporated into the methods and systems to maintain structural integrity after or during a thermal event.
[0036] In embodiments of the methods and systems, the compressible thermal barrier is provided as a single layer of insulating material. In embodiments, the insulating material is in the form of an aerogel. In some embodiments, the aerogel may be formed of a composite material. In some embodiments, the aerogel may include additives. Typically, the insulating material is compressible.
[0037] Some embodiments of the present disclosure feature a single layer thermal barrier disposed between adjacent cells, but the present disclosure is not limited to single layer materials. For example, some embodiments feature multi-layer materials for use as thermal barriers in electrical energy storage systems to solve the problem of heat propagation in battery modules or battery packs, and to stop or mitigate heat propagation when one cell causes thermal runaway. The unique configuration of the multi-layer materials of the present disclosure can help solve the problem of heat propagation between cells. In general, multi-layer thermal barriers include one or more layers of insulating material. It is the size or amount of the insulating layer that is adjusted according to the present disclosure to mitigate heat propagation.
[0038] In one aspect, a multilayer material provided herein for use as a thermal barrier in an electrical energy storage system includes a core including a layered set of at least one insulating layer and at least one heat capacitive layer stacked in an alternating manner in a direction perpendicular to its largest surface, and an exterior disposed outside the core including at least one sacrificial material layer including a compressible pad and at least one encapsulating material layer selected from a polymer, an elastomer, or a combination thereof. Without wishing to be bound by theory, it is believed that in selecting a given dimension of a thermal barrier including a multilayer material, the dimension selected to prevent heat propagation therefrom is incorporated into the thickness of the insulating layer(s) of the multilayer material.
[0039] In one or more embodiments, the multilayer material according to any of the above aspects has an average thickness in the uncompressed state in the range of about 2 mm to about 10 mm. In some embodiments, the thickness of the insulating layer in the multilayer material in the uncompressed state has a thickness in the range of about 1 mm to about 7 mm. In some embodiments, the insulating layer of the multilayer material has a predetermined size (e.g., thickness) in the uncompressed state in the range of 1.5 mm to about 5 mm. In the compressed state, the insulating layer can have a thickness of about 0.75 mm to about 2.5 mm, such as about 1.25 mm or about 1.5 mm.
[0040] Embodiments of the above aspects, methods, and systems may include one or more of the following features. In some embodiments, the insulating layer(s) (if a multi-layer material is used for the thermal barrier) or the single layer thermal barrier comprises an aerogel and optionally further comprises a reinforcing material. In some embodiments, the reinforcing material is a fiber selected from organic polymer-based fibers, inorganic fibers, carbon-based fibers, or combinations thereof. In some embodiments, the fiber is in the form of separate fibers, woven materials, dry-laid nonwoven materials, wet-laid nonwoven materials, needle-punched nonwovens, batting, webs, mats, felts, and / or combinations thereof. In some embodiments, the inorganic fibers are selected from glass fibers, rock fibers, metal fibers, boron fibers, ceramic fibers, basalt fibers, or combinations thereof. In one or more embodiments, the aerogel comprises a silica-based aerogel. In one or more embodiments, the aerogel comprises one or more additives, the additives being present at a level of at least about 5-40 weight percent of the aerogel, preferably at a level of at least about 5-20 weight percent of the aerogel, more preferably at a level of at least about 10-20 weight percent of the aerogel. In some embodiments, the one or more additives comprise a fire-rated additive. In some embodiments, the one or more additives comprise an opacifying agent selected from B4C, diatomaceous earth, manganese ferrite, MnO, NiO, SnO, Ag2O, Bi2O3, TiC, WC, carbon black, titanium dioxide, iron titanium oxide, zirconium silicate, zirconium oxide, iron (I) oxide, iron (III) oxide, manganese dioxide, iron titanium oxide (ilmenite), chromium oxide, or mixtures thereof. In some embodiments, the one or more additives comprise an opacifying agent comprising silicon carbide. In some embodiments, the one or more additives comprise a combination of a fire-rated additive and an opacifying agent. In one or more embodiments, the aerogel has a density ranging from about 0.25 g / cc to about 1.0 g / cc. In one or more embodiments, the aerogel is in the form of a monolith, beads, particles, granules, powder, thin film, sheet, or combinations thereof.
[0041] In another embodiment, a multi-layer material for use as a thermal barrier in an electrical energy storage system includes a core portion including an insulating layer, the insulating layer having a thermal conductivity of less than about 50 mW / m·K at 25° C. and less than about 60 mW / m·K at 600° C. through a thickness dimension of the insulating layer, and an exterior portion disposed outside of the core portion, the exterior portion including a thermally conductive layer, the thermally conductive layer having a thermal conductivity of at least about 200 mW / m·K along an in-plane dimension of the thermally conductive layer.
[0042] In an embodiment, the thermally conductive layer is divided into a first conductive layer and a second conductive layer on either side of the insulating layer, and the first conductive layer and the second conductive layer are in contact with the insulating layer. In a particular embodiment, the thermally conductive layer is substantially L-shaped, such that a vertical portion of the L-shaped thermally conductive layer is spaced apart from the insulating layer. A horizontal portion of the L-shaped thermally conductive layer is in contact with the insulating layer. One or more of an encapsulating material layer, a sacrificial material layer, and a heat capacity layer may be disposed between the vertical portion of the L-shaped thermally conductive layer and the insulating layer.
[0043] In an embodiment, the battery module includes a first battery cell having a first surface, a second battery cell having a second surface, the second surface facing the first surface, and a multi-layer material having a core including an insulating layer and an exterior disposed outside the core, the exterior including a thermally conductive layer. The battery module further includes a heat exchange system in contact with the first battery cell, the second battery cell, and the thermally conductive layer of the multi-layer material. In an embodiment, the multi-layer material covers at least about 80% of the surface area of the opposing first and second surfaces. In one embodiment, the insulating layer of the multi-layer material extends into the heat exchange system.
[0044] The thermally conductive layer of the multi-layer material is in thermal communication with the heat exchange system and with one of the battery cells. The thermal communication between the multi-layer material and the battery cell may be achieved by placing the thermally conductive material in contact with a surface of the battery cell. This configuration allows heat generated by the battery cell to be drawn into the heat exchange system through the thermally conductive layer.
[0045] Heat transfer from a battery cell undergoing thermal runaway can be inhibited or minimized by placing an appropriate multi-layer material between the battery cells. In an embodiment, the multi-layer material has a thermal resistance coefficient of at least 0.01. The thermal resistance coefficient is the ratio of the thermal resistance of the multi-layer material to the areal energy density of the battery cells in the battery module. The areal energy density of the battery cell array is the ratio of the total energy density of all cells in the array to the external surface of the array. The multi-layer material may also have a thickness factor of at least about 0.3. The thickness factor is the ratio of the thickness of the multi-layer material to the areal energy density of the battery cells.
[0046] In an embodiment, a method for designing an energy storage system includes assembling one or more battery cell(s) to form an array, calculating an areal energy density of the array, selecting a thermal resistance and a compressed thickness of a multi-layer material according to the areal energy density of the array such that the energy storage system has a thermal resistance coefficient of at least about 0.01 and a thickness coefficient of at least about 0.3, and disposing the multi-layer material within and / or around the array. In one embodiment, the cell areal energy density of the array is known. Selecting a compressed thickness of a multi-layer material capable of suppressing runaway propagation includes, in this embodiment, calculating a thermal resistance coefficient of the multi-layer material, reading from a heat propagation map a minimum compressed thickness of the multi-layer material, and selecting a compressed thickness greater than the minimum compressed thickness. Similarly, selecting a thermal resistance and a compressed thickness can also be achieved by calculating a thickness coefficient of a multi-layer material that can be placed between battery cells of the array, reading from a heat propagation map a minimum thermal resistance of the multi-layer material, and selecting a thermal resistance of the multi-layer material greater than the minimum thermal resistance.
[0047] In another aspect, the device or vehicle provided herein comprises the battery module or battery pack according to any one of the above aspects.In some embodiments, the device is a laptop computer, a PDA, a mobile phone, a tag scanner, an audio device, a video device, a display panel, a video camera, a digital camera, a desktop computer, a military portable computer, a military telephone, a laser range finder, a digital communication device, a secret information gathering sensor, an electronic integrated garment, a night vision device, a power tool, a calculator, a radio, a remote control device, a GPS device, a handheld and portable television, a car starter, a flashlight, an acoustic device, a portable heating device, a portable vacuum cleaner, or a portable medical tool.In some embodiments, the vehicle is an electric car.
[0048] The methods and systems described herein may provide one or more advantages over existing thermal runaway mitigation solutions. The multi-layer materials described herein can minimize or eliminate cell heat propagation and assembly costs without significantly affecting the energy density of the battery module or battery pack. Some embodiments of the systems and methods of the present disclosure can provide favorable properties in terms of compressibility, compressive resiliency, and compliance to accommodate continued cell expansion over the life of the cell, while retaining favorable thermal properties under normal operating conditions and under thermal runaway conditions. Some embodiments of the methods and systems described herein are durable, easy to handle, favorable resistance to heat propagation and fire propagation while minimizing the thickness and weight of the materials used, and also have favorable properties in terms of compressibility, compressive resiliency, and / or compliance.
[0049] The present disclosure has therefore been described in general terms and reference is now made to the accompanying drawings, which are not necessarily drawn to scale. [Brief description of the drawings]
[0050] [Figure 1] FIG. 1 is a schematic diagram of an electrochemical cell of a Li-ion battery. [Diagram 2] FIG. 1 is a schematic diagram of the charge and discharge process of a Li-ion battery. [Diagram 3] 1 illustrates a schematic of a thermal runaway harsh condition and a thermal runaway propagation process in a battery module. [Figure 4] FIG. 1 is a schematic diagram of dendritic growth on lithium plating of a battery. [Diagram 5] 1 shows a schematic of the three stages that lead to a thermal runaway process. [Figure 6] 1 illustrates a schematic diagram of a battery cell, a battery module, and a battery pack. [Figure 7] 7A and 7B are schematic diagrams of an embodiment of a method for preventing heat propagation from a trigger cell (i.e., a cell undergoing thermal runaway) to adjacent cells, respectively, and a front view of a test setup for testing the heat propagation functionality of a thermal barrier according to embodiments disclosed herein. [Figure 8] 7C is a graph showing the temperature of a trigger cell (i.e., the cell undergoing thermal runaway) versus adjacent cells tested using the setup shown in FIG. 7B. [Figure 9A] 7B shows the results of several cells with different thermal barrier thicknesses between the trigger cell and the adjacent cell, as tested in the setup shown in FIG. 7B. [Figure 9B] 7B shows the results of several cells with different thermal barrier thicknesses between the trigger cell and the adjacent cell, as tested in the setup shown in FIG. 7B. [Figure 9C] 7C is a table providing parameters of several different prismatic and pouch cells that were tested using the setup shown in FIG. 7B. [Figure 10] 1 illustrates a schematic representation of a multi-layer material, according to certain embodiments disclosed herein. [Figure 11] 1 illustrates a schematic representation of a multi-layer material, according to certain embodiments disclosed herein. [Figure 12A] 1 illustrates a schematic representation of a multi-layer material, according to certain embodiments disclosed herein. [Figure 12B]1 illustrates a schematic representation of a multi-layer material, according to certain embodiments disclosed herein. [Figure 12C] 1 illustrates a schematic representation of a multi-layer material, according to certain embodiments disclosed herein. [Figure 12D] 1 illustrates a schematic representation of a multi-layer material, according to certain embodiments disclosed herein. [Figure 12E] 1 illustrates a schematic representation of a multi-layer material, according to certain embodiments disclosed herein. [Figure 13] 1 shows a schematic representation of a multi-layer material having a core insulating layer. [Figure 14] 1 is a flowchart outlining a method for manufacturing a battery cell module. [Figure 15] 1 illustrates a schematic diagram of a battery module or pack having multiple battery cells protected by a multi-layer material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0051] In the following detailed description of the preferred embodiments, reference is made to the accompanying drawings which form a part hereof, and in which is shown, by way of illustration, specific embodiments in which the present disclosure may be practiced. It is to be understood that other embodiments may be utilized and structural changes may be made without departing from the scope of the present disclosure.
[0052] In general, the present technology is directed to systems and methods for mitigating thermal events, such as thermal runaway problems, in energy storage systems. Specifically, the present technology provides systems, methods, and techniques for preventing thermal propagation from occurring in adjacent cells, modules, or packs after a portion of a battery-based energy storage system experiences a thermal event (e.g., thermal runaway). The present disclosure further relates to battery modules or battery packs having one or more battery cells that include an amount (e.g., thickness, volume, etc.) of thermal barrier material according to the present technology to mitigate thermal propagation, as well as systems including those battery modules or battery packs.
[0053] FIG. 7A illustrates a method of preventing heat transfer between adjacent cells according to the present technology. FIG. 7A illustrates a trigger cell (i.e., a thermally damaged cell) in an energy storage system. The trigger cell is sandwiched between two adjacent cells. The adjacent cells have not yet been damaged by the heat emitted by the trigger cell. A thermal barrier material is sandwiched between each adjacent cell and the trigger cell. During use of the energy storage system, the thermal barrier material (labeled C2C barrier in FIG. 7A) is compressed and covers the inter-cell surfaces between the adjacent cells and the trigger cell. Typically, the energy storage system is provided with a cooling plate in thermal contact with all the cells. The cooling plate in FIG. 7A is shown at the bottom of the storage system. To prevent heat transfer between the cells, a thermal barrier material (labeled C2C barrier in FIG. 7A) is sandwiched between the adjacent cells and the trigger cell. * and the total radiation potential is 5E * For a trigger cell, four primary energy flows are considered. First, (1) conduction from the trigger cell to adjacent cells must be addressed. As shown in Figure 7A, approximately 0.15E conduction flows through each face of the trigger cell. *Second, (2) some of the heat released from the trigger cell is removed by conduction to the cooling plate. The amount of heat absorbed from the cooling plate depends on the type of cooling plate used, with a larger amount of heat being removed with the application of active cooling. Third, (3) some heat will be released as solids, liquids, and / or gases emitted from the trigger cell. This heat is vented to the headspace of the energy storage system. Finally, (4) if the trigger cell were to burn, the amount of heat released would depend on the presence or absence of oxygen and the chemical decomposition pathway. To address heat propagation and provide the longest protection from the heat release of the trigger cell to the adjacent cells from damage, both the heat conduction from the trigger cell and the management of the gases and materials released should be addressed. In addressing the issue of conduction between the trigger cell and the adjacent cells, the thermal barrier material of the present technology provides excellent mechanical and thermal properties. That is, the thermal barrier material manages two important aspects that occur at the interface between the cells. First, the thermal barrier material absorbs mechanical energy (high stresses and strains) with minimal fatigue or compression set, allowing the cells to expand and degas, and second, the thermal barrier material can withstand temperatures of over 1000°C (up to 1400°C) even when compressed, allowing the slowing or prevention of heat propagation.
[0054] It is desirable for the thermal barrier material between adjacent cells to be compressible and able to absorb volumetric variations during operation of the energy storage system. It is an objective of the present disclosure to provide not only a compressible thermal barrier, but also a thermal barrier that can mitigate heat propagation from a damaged cell (e.g., a burning cell in a thermal runaway) to adjacent cells. To mitigate heat propagation, adjacent (i.e., not yet damaged) cells cannot exceed a critical temperature at which thermal runaway occurs. To do so, the present technology adjusts the size of its compressible thermal barrier based on the cell's cell areal energy density. As used herein, cell areal energy density is defined as the ratio of the total energy density of all cells in the array to the exterior surface of the array of cells divided by the area of the heat transfer surface of the cell. Without wishing to be bound by theory, it is believed that protection can be achieved by adjusting the compressed thickness of the thermal barrier in relation to the areal energy density of a particular cell. It is further believed that a linear relationship between the compressed thickness and areal energy density of the thermal barrier can be utilized to determine the desired amount / thickness of the compressible thermal barrier (in the uncompressed state).
[0055] To determine the relationship between areal energy density and thickness, a test setup was designed and assembled. The test setup is shown in FIG. 7B. The test setup includes two clamping surfaces that compress the trigger cell (i.e., the cell that will be damaged during the test) and an adjacent cell together. A thermal barrier is sandwiched between the two cells. FIG. 7B shows the pre-test, i.e., uncompressed, image. The thermal barrier shown sandwiched between the trigger cell and the adjacent cell has a thickness of 2.35 mm. Other thicknesses are possible, including 2x, 3x, and 4x the thickness of the 2.35 mm thick thermal barrier. Different tests can be performed to evaluate the thickness of the thermal barrier.
[0056] Each of the trigger cell and adjacent cell in the embodiment of FIG. 7B is a prismatic cell, each with a storage capacity of 62 Ah. To begin the test, the clamp faces are pressed together to apply pressure to the cell faces. Referring to FIG. 8, testing a 4.7 mm thick thermal barrier (i.e., twice the thickness of the 2.35 mm shown in FIG. 7B) produces a cell face pressure of 560 kPa. As can be seen on the right side of FIG. 8, this cell face pressure remains relatively stable until the trigger cell begins to undergo the first stage of a thermal event. As the voltage on the trigger cell decreases, the pressure on the cell face initially increases until an extreme temperature change occurs in the trigger cell. This extreme temperature change is believed to correspond to a combustion event (i.e., flame initiation and leakage from the trigger cell). This combustion event is noted on the time scale as occurring at time zero, indicating the beginning of vigorous thermal runaway of the trigger cell.
[0057] Over the next few minutes of testing, the trigger cell undergoes thermal runaway, except that a 4.7mm thick thermal barrier (measured in uncompressed condition) protects the adjacent cells from the dissipation of heat, preventing them from exceeding a critical temperature (i.e., the temperature of the trigger cell at time 0 minutes).
[0058] By protecting the adjacent cells from the heat dissipated from the trigger cell, the adjacent cells remain below the critical temperature even though the trigger cell (which is in close proximity to it) is experiencing thermal runaway. As a result, a 4.7 mm thick incompressible thermal barrier (formed of aerogel) mitigates or prevents heat transfer between the two prismatic cells, each with a stored energy capacity of 62 Ah.
[0059] The multi-layer material used in the example described in FIG. 8 includes a thermally conductive layer, a thermally absorbing layer, a thermally resistant layer, and a thermal barrier layer. Each of these layers blocks or removes heat generated from the adjacent battery cells. However, some layers play different roles in certain stages of the runaway process. In the first stage, the battery is operating under normal operating conditions, and the outer thermally conductive layer (thermal conduction layer) extracts heat from the adjacent battery cells and directs it to the heat exchange element. In stage 2 of the runaway process, the temperature of the battery cells starts to increase significantly (to temperatures above 90° C.), which starts to cause the battery cells to fail. Some of the heat continues to be carried by the thermally conductive layer, for example to the heat exchange element. The excess heat generated by the battery cells is absorbed by the thermally absorbing layer (thermal capacitance layer). As the runaway process continues, the rapid temperature increase exceeds the capacity of the first two heat sink systems (thermal conduction layer and thermal capacitance layer). The heat then reaches the heat-resistant layer (sacrificial layer), which absorbs some of the heat generated by the runaway cell as the layers decompose. The last layer to prevent the heat from the runaway battery cell from reaching other cells is the insulating layer. After passing through these first three layers, the heat has been dissipated sufficiently so that the insulating layer can prevent the heat from reaching the neighboring cells. As shown in Figure 8, the temperature of the neighboring battery cells is kept below 100°C by the multi-layer barrier.
[0060] Referring to FIG. 9, four test samples were tested using the test setup shown in FIG. 7B to generate the results and performance maps. Test samples AAI T1 and AAI T3 had an uncompressed thickness of 2.35 mm, while test samples AAI T2 and AAI T4 had an uncompressed thickness of 4.70 mm (twice that of T1 and T3). The cell face pressure (CFP) applied or generated for test sample AAI T1 was 275 kPa, for AAI T2 275 kPa, for AAI T3 580 kPa, and for AAI T4 560 kPa. The areal energy density (kAh / m 2 ) is about 2kAh / m 2 It was.
[0061] FIG. 9 shows that when the compression force (i.e., cell face pressure) is less than 300 kPa (specifically 275 kPa), the thickness of the thermal barrier between the two cells shown in FIG. 7B, 2.35 mm or 4.70 mm, is sufficient to mitigate / prevent heat transfer between the cells. In fact, the delay or protection given to the adjacent cells continued until the thermal event of the trigger cell was terminated (i.e., after all heat had dissipated from the trigger cell, until the combustion was terminated). The thermal barrier of the uncompressed thickness is tested when the pressure on the cell face is increased by more than twice (i.e., more than 560 kPa). The AAI T3 sample with a thickness of 2.35 mm somewhat mitigates the heat transfer to the adjacent cells (delay of 28 minutes). By doubling the thickness of the thermal barrier (i.e., test sample AAI T4) to 4.70 mm, the prevention of heat transfer to the adjacent cells was achieved.
[0062] A performance map was generated by testing thermal barriers of various thicknesses under various compression conditions for various cell types and configurations. The dashed lines in the performance map displayed on the right side of FIG. 9A show the relationship between areal energy density and the compressed thickness of the barrier. Clearly, the greater the compression applied / created at the cell face, the less the compressed thickness of the thermal barrier material. This information can be used to select a given magnitude (i.e.) thickness of the thermal barrier in the uncompressed state.
[0063] FIG. 9B illustrates a heat propagation map showing the relationship between thermal resistance and cell areal energy density, and between thickness at compression and cell areal energy density. Given one of these three variables, the values of the other two properties can be determined using the heat propagation map. In many situations, the cell areal energy density is known due to the energy demands of the system being powered. Based on the known cell areal density, a multi-layer material can be selected to ensure that a barrier is used that will limit or minimize the risk of propagation when the battery cell goes into thermal runaway. In other situations, the multi-layer material may already be pre-selected. In other situations, based on the known thermal resistance of the material, a cell areal energy density can be selected to ensure that propagation is limited or minimized.
[0064] In the particular example used to generate the heat propagation map of FIG. 9B, an aerogel material was used. In this example, the upper lighter shaded area (above the dashed transition line) is an area where no or only little runaway propagation should occur. In general, the heat propagation map shows a thermal resistance coefficient of at least about 0.01, and a thickness factor of at least about 0.3, with a maximum of about 14 kWh / m 2 It is shown that the thermal propagation map would be effective in suppressing or minimizing the propagation of runaway battery cells for cell areal energy densities up to 1000 nm. Extrapolation of the heat propagation map can be used to determine optimal parameters for higher cell areal densities. Thickness factor is defined herein as the ratio of the thickness of the multilayer material to the areal energy density of the array. Thermal resistance factor is defined herein as the ratio of the thermal resistance of the multilayer material to the areal energy density of the array.
[0065] FIG. 14 shows a flow chart 100 outlining a process for designing an insulation system for a battery cell or battery module. In step 110, one or more battery cells or battery modules are assembled into an array with some gaps between each of the battery cells / modules. In step 120, the areal energy density of the array is calculated. The areal energy density can then be used in step 130 to determine the thermal resistance and compressed thickness of the multi-layer material. The thermal resistance and compressed thickness are selected to inhibit or minimize heat propagation from a runaway battery cell / module.
[0066] Step 130 may be divided into two sub-steps. In one embodiment, the thermal resistance coefficient of the multilayer material is determined, as shown on the left side of step 130. The thermal resistance coefficient of the multilayer material is then used in combination with the areal energy density of the array to determine the thickness of the multilayer material needed to suppress or minimize thermal runaway propagation. Selection of the compressed thickness of the multilayer material that can suppress runaway propagation may be done by reading the minimum compressed thickness of the multilayer material from a thermal propagation map such as shown in FIG. 9B. The multilayer material having the determined thickness is then placed in the array.
[0067] In an alternative embodiment, step 130 may be performed by determining a thickness factor of a multi-layer material that may be placed between battery cells of the array. Using the determined thickness factor, a thermal resistance of the multi-layer material needed to inhibit or minimize thermal runaway propagation may be determined. In one embodiment, a minimum thermal resistance of the multi-layer material may be determined from a thermal propagation map such as that shown in FIG. 9B. The thermal resistance of the multi-layer material is selected by determining a thermal resistance of the multi-layer material that is greater than the minimum thermal resistance of the multi-layer material needed to inhibit or minimize thermal runaway propagation. The multi-layer material having the determined thermal resistance is then placed in the array.
[0068] In one embodiment, disposing the multi-layer material in and / or around the array includes forming the multi-layer material separately from the array and inserting the multi-layer material next to the battery cells of the array. In another embodiment, disposing the multi-layer material in and / or around the array includes forming the multi-layer material in situ directly in and / or around the array. The multi-layer material can be formed in situ by spraying, coating, depositing, or filling the multi-layer material in and / or around the array.
[0069] FIG. 15 illustrates various configurations of battery cells and multi-layer materials that can be used to inhibit or minimize thermal propagation. In a first configuration, the multi-layer material is placed between individual battery cells or battery modules such that each battery cell / module is individually surrounded by the multi-layer material. In a second configuration, multiple battery cells / modules are in contact with each other. The number of cells that can be stacked adjacent to each other without a barrier between the cells is based on the areal energy density of the combined stacked cells and the properties of the barrier (such as thermal resistance), i.e., based on the method shown in FIG. 14. The multi-layer material surrounds a group of battery cells / modules to inhibit or minimize thermal runaway propagation from any of the surrounded cells. The second configuration can be useful for high density energy systems where there is not much space available for a thermal barrier such as the multi-layer material described herein. In a third configuration, the multi-layer material is placed between each of the battery cells / modules such that the multi-layer material used to protect one of the battery cells / modules is also used to protect the adjacent battery cell / module.
[0070] 9C, a table is shown providing various parameters and calculated areal energy densities for a number of prismatic and pouch cells produced by different manufacturers. The calculated areal energy densities can be used in conjunction with the compression directed between the cells to select the thickness of the thermal barrier material.
[0071] The thermal barriers used in producing Figures 9A and 9B are formed of an aerogel material available from Aspen Aerogels, Inc., Northborough, MA. The particular material used is sold under the trade name PyroThin® and is a thin, lightweight, high temperature thermal insulating material. Without wishing to be bound by theory, the Aspen Aerogels, Inc. aerogel is advantageous for at least three reasons. First, this particular aerogel material is resilient. When comparing compressive stress and compressive strain during loading and unloading events, only minimal hysteresis is observed. That is, this aerogel material is resilient. It is believed that the silica polymer long chains act together as a mass of elastic nanosprings to create a resilient compression pad that absorbs mechanical energy with minimal fatigue or compression set. Aspen Aerogels, Inc. manufactures and sells a reinforced M grade material sold under the trade name PyroThin®. M-grade materials are known to resist compression set (≦5%) and are not susceptible to fatigue. Another advantage of this particular material is its ability to withstand high temperatures, including temperatures of 1400°C or higher. In general, this particular aerogel material can withstand direct flame contact at temperatures of 1000°C for over 10 minutes. That is, even after 10 minutes of exposure to an open flame, the aerogel material did not burn or even begin to disintegrate. This silica-based aerogel containing inorganic fibers is tunable with respect to its thermal properties. As a result, the temperature resistance of the aerogel material can be tailored to match the behavior of the cell. Aspen Aerogels, Inc.'s silica-based aerogels provide beneficial thermal conduction properties even when compressed, and as a result, are advantageous for use as thermal barrier materials according to the present technology. Without wishing to be bound by theory, it is believed that aerogels do not rely on trapped air to provide a thermal advantage. As a result, the aerogel material maintains its thermal conduction properties even when compressed.This means that the thermal barrier materials that provide these advantages to systems according to the present technology can be provided with thinner barriers, lighter packs, and a wider range of cells.
[0072] The present technology can also be applied to thermal barrier materials that are not simply monolayer materials. For example, in the present technology, the thermal barrier disposed between cells may have a multilayer configuration. This multilayer configuration includes one or more insulating layer(s) sized to prevent thermal propagation between cells. That is, the thermal barrier includes a variety of layers in a multilayer configuration, but the thickness of the insulating layer(s) in the uncompressed state is selected with knowledge of the areal energy density using the methods and systems described for the monolayer embodiment.
[0073] Thermal barriers including multiple layers may add additional benefits such as mechanical strength, expansion layers, and encapsulation of materials. The following description of multi-layer materials may be used in the present technology in place of single-layer embodiments or in addition to single-layer thermal barriers as a complement to the system. For example, some systems may include single-layer thermal barriers in some locations and multi-layer thermal barriers in other locations. That is, a single-layer thermal barrier is provided between some adjacent cells while a multi-layer thermal barrier is provided between other adjacent cells. In some embodiments, a single-layer thermal barrier is provided between adjacent cells and a multi-layer material is used as a thermal barrier around the edges or faces of the energy system.
[0074] In the present technology, multi-layer materials and systems including such multi-layer materials can be used to manage thermal runaway problems in energy storage systems. An exemplary embodiment includes a multi-layer material including at least one insulating layer, at least one compressible pad, and one or more optional layers. The optional one or more layers have favorable heat dissipation properties, favorable fire resistance properties, flame retardant properties, and / or abrasion resistance properties, and favorable performance for use as a thermal barrier. The present disclosure further relates to a battery module or battery pack with one or more battery cells and a multi-layer thermal barrier material disposed in thermal communication with the battery cells.
[0075] One or more of the insulating layers of the multi-layer materials disclosed herein may include an aerogel composition or a reinforced aerogel composition. Aerogel materials are known to possess thermal resistance approximately 2-6 times that of other common types of insulation, e.g., foam, fiberglass, etc. Aerogels can improve effective shielding and insulation without substantially increasing the thickness of the insulation or adding additional weight. Aerogels are known to be a structural class that has low density, open cell structure, large surface area, and nanometer-scale pore size.
[0076] Multilayer materials according to embodiments of the present disclosure and including aerogel compositions provide favorable properties of compressibility, compressive resiliency, and compliance. When used as a thermal barrier between cells in a battery module, the multilayer materials can provide resistance to compressive deformation to accommodate cell expansion due to degradation and expansion of active materials during battery charge / discharge cycling.
[0077] The present disclosure also provides a battery module or battery pack including at least one battery cell and a multi-layer material according to an embodiment disclosed herein disposed on the battery cell or battery module, e.g., disposed on a surface of at least one battery cell or on a surface of the battery module. For example, the battery module or battery pack has an interior surface and an exterior surface. In certain embodiments, the multi-layer material is on the interior surface of the battery module or battery pack. In certain embodiments, the multi-layer material is on the exterior surface of the battery module or battery pack.
[0078] The multi-layer material of the present disclosure may have a variety of unique configurations in which two or more layers having favorable thermal and / or mechanical properties are arranged in a specific manner. FIG. 10 illustrates an exemplary multi-layer material 400 according to an embodiment disclosed herein. In one embodiment, a multi-layer material 400 for use as a thermal barrier in an electrical energy storage system includes a core portion 700 including a layered assembly of insulating layers 470 and 480 and heat capacity layers 430, 440, and / or 450 stacked alternately in a direction perpendicular to the largest surface, and an exterior portion 600 disposed outside the core portion 700, each of the exterior portions 600 having a sacrificial material layer including a compressible pad. The compressible pads 410 / 460 have a compression modulus of about 1 MPa to about 12 MPa. The encapsulating material layer 420 is selected from a polymer, an elastomer, or a combination thereof. The heat capacity layers 430, 440, and 450 have a specific heat capacity of at least about 200 J / (kg·K). Insulating layers 470 and 480 have a thermal conductivity through the thickness dimension of the insulating layers of less than about 50 mW / m·K at 25° C. and less than about 60 mW / m·K at 600° C.
[0079] In some embodiments, insulating layers 470 and 480 are made from the same material. In some embodiments, insulating layers 470 and 480 are made from different materials having different thermal and / or mechanical properties. In some embodiments, thermal capacity layers 430, 440, and 450 are made from the same material. In some embodiments, thermal capacity layers 430, 440, and 450 are made from different materials having different thermal and / or mechanical properties. Also, compressible pads 410 and 460 can be made from different materials or the same material.
[0080] FIG. 11 illustrates a multi-layer material 500 according to an embodiment disclosed herein. In one embodiment, the multi-layer material 500 for use as a thermal barrier in an electrical energy storage system includes a core portion 700 including a layered assembly of insulating layers 470 and 480 and thermally conductive layers 530, 540, and 550 stacked in an alternating manner in a direction perpendicular to the largest surface. An exterior portion 600 is disposed outside the core portion 700. The exterior portions 600 each include a sacrificial material layer including a compressible pad. The compressible pads 410 / 460 have a compression modulus of about 1 MPa to about 12 MPa. The encapsulating material layer 420 is selected from a polymer, an elastomer, or a combination thereof. The thermally conductive layers 530, 540, and 550 have a thermal conductivity of at least about 200 mW / m·K along an in-plane dimension of the thermally conductive layer. Insulating layers 470 and / or 480 have a thermal conductivity through the thickness dimension of the insulating layer of less than about 50 mW / m·K at 25° C. and less than about 60 mW / m·K at 600° C.
[0081] In some embodiments, thermally conductive layers 530, 540, and 550 are made from the same material. In some embodiments, thermally conductive layers 530, 540, and 550 are made from different materials having different thermal and / or mechanical properties.
[0082] 10 and 11, the encapsulation material layer 420 is sandwiched between the core portion 700 and a sacrificial material layer having at least one compressible pad 410 and / or 460. In some embodiments, the sacrificial material layer having at least one compressible pad 410 and / or 460 is sandwiched between the core portion 700 and the encapsulation material layer 420.
[0083] The multilayer material according to embodiments disclosed herein may have an average thickness in the uncompressed state ranging from about 2 mm to about 10 mm. The average thickness of the multilayer material may decrease when exposed to an external mechanical load, such as a load of up to 1 MPa, such as a load applied to the material between the cells during initial assembly of the battery module.
[0084] In an exemplary configuration of the multi-layer material shown in Figure 12A, a multi-layer material 800 for use as a thermal barrier in an electrical energy storage system includes a core layer with compressible pads 410 having a compression modulus of about 1 MPa to about 12 MPa (e.g., 1.5 MPa, 2 MPa, 4 MPa, 5 MPa, 6 MPa, 8 MPa, 9 MPa, 10 MPa, 11 MPa, 11.5 MPa) and two insulating layers 470 and 480 having a thermal conductivity through the thickness dimension of the insulating layer of less than about 50 mW / m·K at 25°C and less than about 60 mW / m·K at 600°C. The core layer is sandwiched between the two insulating layers 470 and 480, and the multi-layer material is optionally encapsulated in an encapsulating material 420 selected from at least one of a polymer, an elastomer, or a combination thereof.
[0085] In an exemplary configuration of the multi-layer material shown in FIG. 12B, a multi-layer material 810 for use as a thermal barrier in an electrical energy storage system includes a core layer including a compressible pad 410 having a compression modulus of about 1 MPa to about 12 MPa and two thermally conductive layers 530 and 540. The multi-layer material 801 also includes two insulating layers 470 and 480 having a thermal conductivity of less than about 50 mW / m·K at 25° C. and less than about 60 mW / m·K at 600° C. through a thickness dimension of the insulating layers, the core layer being sandwiched between the two insulating layers 470 and 480, the at least one thermally conductive layer having an in-plane thermal conductivity of at least about 200 mW / m·K, and the multi-layer material is optionally encapsulated in an encapsulation material 420 selected from at least one of a polymer, an elastomer, or a combination thereof.
[0086] In an exemplary embodiment shown in FIG. 12C, a multi-layer material 820 for use as a thermal barrier in an electrical energy storage system includes a core layer including a compressible pad 410 having a compression modulus of about 1 MPa to about 12 MPa and two heat capacity layers 430 and 440. The core layer is sandwiched by two insulating layers 470 and 480 having a thermal conductivity of less than about 50 mW / m·K at 25° C. and less than about 60 mW / m·K at 600° C. through the thickness dimension of the insulating layers. The heat capacity layers have a specific heat capacity of at least about 200 J / (kg·K). The multi-layer material is optionally encapsulated in an encapsulation material 420 selected from at least one of a polymer, an elastomer, or a combination thereof.
[0087] In an exemplary embodiment shown in FIG. 12D, a multi-layer material 830 for use as a thermal barrier in an electrical energy storage system includes a core layer having a compressible pad 410 having a compression modulus of about 1 MPa to about 12 MPa and two heat capacity layers 430 and 440. Two insulating layers 470 and 480 having a thermal conductivity of less than about 50 mW / m·K at 25° C. and less than about 60 mW / m·K at 600° C. through the thickness dimension of the insulating layers sandwich the core layer. The heat capacity layers have a specific heat capacity of at least about 200 J / (kg·K). The multi-layer material 830 further includes two additional heat capacity layers 435 and 445 disposed on the outer surface of each insulating layer 470 and 480. The multi-layer material is optionally encapsulated in an encapsulation material 420 selected from at least one of a polymer, an elastomer, or a combination thereof.
[0088] In an exemplary configuration of the multi-layer material shown in FIG. 12E, a multi-layer material 840 for use as a thermal barrier in an electrical energy storage system includes a core layer including two compressible pads 410 and 460, each having a compression modulus of about 1 MPa to about 12 MPa, and one heat capacity layer 430. Two insulating layers 470 and 480, having a thermal conductivity of less than about 50 mW / m·K at 25° C. and less than about 60 mW / m·K at 600° C. through the thickness dimension of the insulating layer, sandwich the core layer. The heat capacity layer has a specific heat capacity of at least about 200 J / (kg·K). The multi-layer material is optionally encapsulated in an encapsulation material 420 selected from at least one of a polymer, an elastomer, or a combination thereof. The heat capacity layer 430 is sandwiched by the two compressible pads 410 and 460.
[0089] In an exemplary configuration of the multi-layer material shown in FIG. 13, a multi-layer material 900 for use as a thermal barrier in an electrical energy storage system includes a core layer including an insulating layer 470 and an exterior including thermally conductive layers 530 and 540. In the illustrated embodiment, the thermally conductive layers 530 and 540 are substantially L-shaped. The vertical portions of the L-shaped thermally conductive layer are spaced apart from the insulating layer. In use, the vertical portions of the L-shaped thermally conductive layer are in thermal or physical contact with the battery cells or battery modules (570, 575, 580). The horizontal portions of the L-shaped thermally conductive layer are in contact with the insulating layer 470 and the heat transfer element 590. The use of the L-shaped thermally conductive layer increases the contact surface area of the thermally conductive layer with the battery cells or battery modules and any heat transfer elements. In use, heat from one or more of the battery cells or battery modules is conducted through the thermally conductive layer to the heat transfer element 590. Thus, heat from the battery cells or battery modules is removed by the heat transfer element. The heat transfer element may be a cooling plate. An exemplary cooling plate includes a fluid transfer (liquid or gas) that removes heat from the heat transfer element during use.
[0090] In an embodiment, one or more of the encapsulation layer (420, 425), the sacrificial material layer (510, 515), and the heat capacity layer (430, 435) are disposed between the vertical portions of the L-shaped thermally conductive layers 530, 540 and the insulating layer 470, as shown in FIG. 13. The sacrificial layer 510 may include a compressible pad having a compression modulus of about 1 MPa to about 12 MPa. The insulating layer 470 has a thermal conductivity through its thickness dimension of less than about 50 mW / m·K at 25° C. and less than about 60 mW / m·K at 600° C. The heat capacity layer (430, 435) has a specific heat capacity of at least about 200 J / (kg·K). The insulating layer is optionally encapsulated in an encapsulation material 420 selected from at least one of a polymer, an elastomer, or a combination thereof. In some embodiments, the encapsulation layer may include a metal layer.
[0091] In use, each of the layers will act as a barrier to prevent heat from the runaway cell from heating other cells. The heat capacity layer will absorb the initial heat of the runaway cell. Heat passing through the heat capacity layer will reach the sacrificial layer, which will absorb the heat as the layer decomposes. Finally, the encapsulation layer will also act as a barrier to reduce the amount of particulate matter impinging on the insulating layer. In an embodiment, the insulating barrier extends at least partially into the heat exchange element 590. The placement of the insulating layer within the heat exchange element is effective in reducing the transfer of heat from a battery cell or battery module undergoing thermal runaway. For example, in some embodiments, the heat from the thermal runaway event will overwhelm the cooling effect of the heat exchange element. Heat from the runaway cell or module may then be conducted through the heat exchange element to other battery cells or battery modules. The portion of the insulating barrier that extends into the heat exchange element inhibits heat from reaching adjacent battery cells or battery modules.
[0092] Insulation layer The insulating layer of the multi-layer material described herein is responsible for reliably controlling the heat flow from the heat generating portion in a small space, providing safety and prevention against fire spread for such products in the fields of electronics, industrial, and automotive technology. A thermal insulation layer with good compressive properties can be useful in addressing these needs. In many embodiments of the present disclosure, the insulating layer also functions as a flame / fire deflection layer, either by itself or in combination with other layers of the multi-layer material. For example, an insulating layer, e.g., an aerogel layer, combined with a non-combustible layer, such as a metal or mica layer, can provide protection for the underlying layer from flame and / or hot gases, as well as from flame / hot gases entrained with particulate materials, such as materials that may be extruded from the LIB during a thermal runaway event. As another example, the insulating layer itself can be resistant to flame and / or hot gases, as well as flame / hot gases entrained with particulate materials. An insulating layer, such as mica, microporous silica, aerogel, etc., can function as a flame / fire deflection layer in combination with a non-combustible layer. Insulation layers comprising aerogel, such as those disclosed in the embodiments herein, are durable, easy to handle, and provide favorable resistance to heat and fire propagation while minimizing the thickness and weight of the material used, as well as favorable properties regarding compressibility, compressive resiliency, and compliance.
[0093] Aerogels are a class of open-celled porous materials that contain an interconnected framework with a corresponding network of pores integrated within the framework, and an interstitial phase within the pore network that consists primarily of a gas, such as air. Aerogels are generally characterized by low density, high porosity, large surface area, and small pore size. Aerogels can be distinguished from other porous materials by their physical and structural properties.
[0094] Thus, in some embodiments, the insulating layer of the multi-layer material of the present disclosure comprises an aerogel. In some embodiments, the insulating layer may further comprise a material selected from the group consisting of mica, microporous silica, ceramic fibers, mineral wool, and combinations thereof. In some cases, the insulating layer lacks aerogel. In some embodiments, the insulating layer may comprise a material selected from the group consisting of mica, microporous silica, ceramic fibers, mineral wool, and combinations thereof.
[0095] In certain embodiments, an insulating layer of the present disclosure has a thermal conductivity at 25° C. through the thickness dimension of the insulating layer of about 50 mW / mK or less, about 40 mW / mK or less, about 30 mW / mK or less, about 25 mW / mK or less, about 20 mW / mK or less, about 18 mW / mK or less, about 16 mW / mK or less, about 14 mW / mK or less, about 12 mW / mK or less, about 10 mW / mK or less, about 5 mW / mK or less, or a range between any two of these values. In certain embodiments, an insulating layer of the present disclosure has a thermal conductivity at 600° C. through the thickness dimension of the insulating layer of about 60 mW / mK or less, about 50 mW / mK or less, about 40 mW / mK or less, about 30 mW / mK or less, about 25 mW / mK or less, about 20 mW / mK or less, about 18 mW / mK or less, about 16 mW / mK or less, about 14 mW / mK or less, about 12 mW / mK or less, about 10 mW / mK or less, about 5 mW / mK or less, or a range between any two of these values.
[0096] Insulation layers of the present disclosure, such as insulation layers comprising aerogel, can retain or increase a small amount of thermal conductivity (usually measured in mW / m·k) when subjected to a load of up to about 5 MPa. In certain embodiments, insulation layers of the present disclosure have a thermal conductivity of about 50 mW / mK or less, about 40 mW / mK or less, about 30 mW / mK or less, about 25 mW / mK or less, about 20 mW / mK or less, about 18 mW / mK or less, about 16 mW / mK or less, about 14 mW / mK or less, about 12 mW / mK or less, about 10 mW / mK or less, about 5 mW / mK or less, or a range between any two of these values, at 25° C. when subjected to a load of up to about 5 MPa through the thickness dimension of the insulation layer. As a result of the load experienced by the aerogel insulation layer, the thickness of the aerogel insulation layer can decrease. For example, the thickness of the aerogel insulation layer may be reduced by 50% or less, 40% or less, 30% or less, 25% or less, 20% or less, 15% or less, 10% or less, 5% or less, or a range between any two of these values when subjected to a load in the range of about 0.50 MPa to 5 MPa. As the thickness is reduced, the thermal resistance of the insulation layer including aerogel may decrease, but the thermal conductivity may be maintained or increased by only a small amount.
[0097] In certain embodiments, an insulating layer of the present disclosure may have a heat of combustion of about 750 cal / g or less, about 717 cal / g or less, about 700 cal / g or less, about 650 cal / g or less, about 600 cal / g or less, about 575 cal / g or less, about 550 cal / g or less, about 500 cal / g or less, about 450 cal / g or less, about 400 cal / g or less, about 350 cal / g or less, about 300 cal / g or less, about 250 cal / g or less, about 200 cal / g or less, about 150 cal / g or less, about 100 cal / g or less, about 50 cal / g or less, about 25 cal / g or less, about 10 cal / g or less, or a range between any two of these values. An insulating layer with an improved heat of combustion relative to another insulating layer has a lower heat of combustion value compared to the reference insulating layer. In certain embodiments of the present disclosure, the HOC of an insulating layer is improved by incorporating a fire-rated additive into the insulating layer.
[0098] In certain embodiments, the insulating layer of the present disclosure has an onset temperature of thermal decomposition of about 300°C or more, about 320°C or more, about 340°C or more, about 360°C or more, about 380°C or more, about 400°C or more, about 420°C or more, about 440°C or more, about 460°C or more, about 480°C or more, about 500°C or more, about 515°C or more, about 550°C or more, about 600°C or more, or a range between any two of these values. Within the context of this specification, for example, for a first composition having an onset temperature of thermal decomposition higher than the onset temperature of thermal decomposition of a second composition, an improvement of the first composition over the second composition would be considered. It is contemplated herein that when adding one or more fire-rated additives, the onset temperature of thermal decomposition of the composition or material increases as compared to a composition without any fire-rated additives.
[0099] The term "flexural modulus" or "flexural modulus of elasticity" is a measure of a material stiffness / resistance to bending when a force is applied perpendicular to the long edge of the sample in what is known as a three-point bend test. Flexural modulus indicates the ability of a material to bend. Flexural modulus is represented by the slope of the initial linear portion of the stress-strain curve and is calculated by dividing the change in stress by the corresponding change in strain. The ratio of stress to strain is therefore a measure of the flexural modulus. The international standard unit of flexural modulus is the Pascal (Pa or N / m 2 or m -l kg s -2 ). The practical units used are megapascals (MPa or N / mm2) or gigapascals (GPa or kN / mm 2 ). In U.S. customary units, it is expressed as pounds (force) per square inch (psi). In certain embodiments, the insulating layer of the present disclosure has a flexural modulus of about 8 MPa or less, about 7 MPa or less, about 6 MPa or less, about 5 MPa or less, about 4 MPa or less, or about 3 MPa or less. Preferably, the insulating layer of the present disclosure, e.g., aerogel, has a flexural modulus of about 2 MPa to about 8 MPa.
[0100] As explained above, the compressive and resilient properties of the materials between the cells or between the battery modules and battery packs are important to accommodate the expansion of the cells during their life cycle. In certain embodiments, the insulating layer, or the multi-layer material including the insulating layer, (i) is compressible to at least 50%, preferably at least 65%, and most preferably at least 80% of its original or uncompressed thickness, and (ii) is sufficiently resilient that after compression for several seconds, the insulating layer returns to at least 70%, preferably at least 75%, and most preferably at least 80% of its original or uncompressed thickness.
[0101] In certain embodiments, the compression modulus of an insulating layer (e.g., a layer comprising an aerogel), a compressible component of a multilayer material comprising an insulating layer, or the multilayer material as a whole is about 1 MPa, about 2 MPa, about 3 MPa, about 4 MPa, about 5 MPa, about 6 MPa, about 7 MPa, about 8 MPa, about 9 MPa, about 10 MPa, about 11 MPa, about 12 MPa, or a range between any two of these values.
[0102] Aerogel The aerogels of the present invention can be organic, inorganic, or mixtures thereof. In some embodiments, the aerogel comprises a silica-based aerogel. The insulating layer of the multi-layer material comprising the aerogel further comprises a reinforcing material. The reinforcing material can be any material that provides resilience, conformability, or structural stability to the aerogel material. Examples of well-known reinforcing materials include, but are not limited to, open-cell macroporous skeletal reinforcement, closed-cell macroporous skeletal reinforcement, open-cell membrane, honeycomb reinforcement, polymeric reinforcement, and fibrous reinforcement such as discrete fibers, woven materials, nonwoven materials, needle-punched nonwovens, batting, webs, mats, and felts.
[0103] The reinforcing material can be selected from organic polymer-based fibers, inorganic fibers, carbon-based fibers, or combinations thereof. The inorganic fibers are selected from glass fibers, rock fibers, metal fibers, boron fibers, ceramic fibers, basalt fibers, or combinations thereof.
[0104] In some embodiments, the reinforcing material may include a reinforcing material that includes a material with multiple layers. For example, the material with multiple layers may be bonded together. In an exemplary embodiment, at least one of the multiple layers may include a first material and at least one other of the multiple layers may include a second material. The first material and the second material may have the same or different material properties. For example, the first material may be more compressible than the second material. As another example, the first material may include closed cells and the second material may include open cells.
[0105] Aerogels are typically described as interconnected structural frameworks composed of interconnected oligomeric, polymeric, or colloidal particles. Aerogel frameworks can be made from a variety of precursor materials, including inorganic precursor materials (such as those used in producing silica-based aerogels), organic precursor materials (such as those used in producing carbon-based aerogels), hybrid inorganic / organic precursor materials, and combinations thereof. Within the context of this disclosure, the term "amalgam aerogel" refers to an aerogel produced from a combination of two or more different gel precursors. The corresponding precursors are referred to as "amalgam precursors."
[0106] Inorganic aerogel Inorganic aerogels are generally formed from metal oxide or metal alkoxide materials. The metal oxide or metal alkoxide materials may be based on the oxide or alkoxide of any metal capable of forming an oxide. Such metals include, but are not limited to, silicon, aluminum, titanium, zirconium, hafnium, yttrium, vanadium, cerium, etc. Inorganic silica aerogels are traditionally made by hydrolysis and condensation of silica-based alkoxides (such as tetraethoxysilane) or by gelation of silicic acid or water glass. Other relevant inorganic precursor materials for the synthesis of silica-based aerogels include metal silicates, including, but not limited to, sodium or potassium silicates, alkoxysilanes, partially hydrolyzed alkoxysilanes, tetraethoxysilane (TEOS), partially hydrolyzed TEOS, condensation polymers of TEOS, tetramethoxysilane (TMOS), partially hydrolyzed TMOS, condensation polymers of TMOS, tetra-n-propoxysilane, partially hydrolyzed and / or condensation polymers of tetra-n-propoxysilane, polyethylsilicates, partially hydrolyzed polyethylsilicates, monomeric alkylalkoxysilanes, bistrialkoxyalkyl or arylsilanes, polyhedral silsesquioxanes, or combinations thereof.
[0107] In certain embodiments of the present disclosure, pre-hydrolyzed TEOS, such as Silbond H-5 (SBH5, Silbond Corp), is hydrolyzed to a water / silica ratio of about 1.9-2, which may be used commercially or may be further hydrolyzed before being incorporated into the gelation process. Partially hydrolyzed TEOS or TMOS, such as polyethylsilicate (Silbond 40) or polymethylsilicate, may also be used commercially or may be further hydrolyzed before being incorporated into the gelation process.
[0108] Inorganic aerogels may also include gel precursors that include at least one hydrophobic group, such as alkyl metal alkoxides, cycloalkyl metal alkoxides, and aryl metal alkoxides, which may impart or improve certain properties of the gel, such as stability and hydrophobicity. Inorganic silica aerogels may specifically include hydrophobic precursors, such as alkyl silanes or aryl silanes. Hydrophobic gel precursors may be used as the primary precursor material to form the framework of the gel material. However, hydrophobic gel precursors are more commonly used as co-precursors in combination with simple metal alkoxides in the formation of amalgam aerogels. Hydrophobic inorganic precursor materials for silica-based aerogel synthesis include, but are not limited to, trimethylmethoxysilane (TMS), dimethyldimethoxysilane (DMS), methyltrimethoxysilane (MTMS), trimethylethoxysilane, dimethyldiethoxysilane (DMDS), methyltriethoxysilane (MTES), ethyltriethoxysilane (ETES), diethyldiethoxysilane, dimethyldiethoxysilane (DMDES), ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane (PhTES), hexamethyldisilazane, hexaethyldisilazane, etc. Any derivative of any of the above precursors may be used, in particular, certain polymers of other chemical groups may be added or crosslinked to one or more of the above precursors.
[0109] Aerogels can also be treated to impart or improve hydrophobicity. The hydrophobic treatment can be applied to a sol-gel solution, a wet gel prior to liquid extraction, or to the aerogel following liquid extraction. Hydrophobic treatment is particularly commonly a product of metal oxide aerogels, such as silica aerogels. Examples of hydrophobic treatment of gels are described in more detail below, specifically with respect to treating silica wet gels. However, the specific examples and illustrations provided herein are not intended to limit the scope of the present disclosure to any particular type of hydrophobic treatment or aerogel substrate. The present disclosure includes any gel or aerogel known to one of skill in the art, as well as related methods of hydrophobic treatment of aerogels, either in wet gel or dry aerogel formation.
[0110] The hydrophobic treatment is carried out by reacting hydroxy moieties on the gel, such as silanol groups (Si-OH) present on the backbone of the silica gel, with the functional groups of the hydrophobizing agent. The resulting reaction converts the silanol groups and the hydrophobizing agent into hydrophobic groups on the backbone of the silica gel. The hydrophobizing agent compound can react with the hydroxyl groups on the gel according to the following reaction: RNMX4-N(hydrophobizing agent)+MOH(silanol)→MOMRN(hydrophobic group)+HX. The hydrophobic treatment can be carried out both on the outer macroscopic surface of the silica gel and on the inner pore surfaces within the porous network of the gel.
[0111] The gel can be immersed in a mixture of a hydrophobizing agent and an optional hydrophobizing solvent in which the hydrophobizing agent is soluble and which is also miscible with the gel solvent of the wet gel. A wide range of hydrophobizing solvents can be used, including solvents such as methanol, ethanol, isopropanol, xylene, toluene, benzene, dimethylformamide, and hexane. Alternatively, a liquid or gaseous hydrophobizing agent can be directly contacted with the gel to render it hydrophobic.
[0112] The hydrophobic treatment process may include mixing or agitation to aid in the penetration of the hydrophobizing agent into the wet gel. The hydrophobic treatment process may also include varying other conditions such as temperature and pH to further enhance and optimize the treatment reaction. After the reaction is complete, the wet gel is washed to remove unreacted compounds and by-products of the reaction.
[0113] Hydrophobizing agents for the hydrophobic treatment of aerogels are generally compounds of the formula: RNMX4-N, where M is a metal, R is a hydrophobic group such as CH3, CH2CH3, C6H6, or similar hydrophobic alkyl, cycloalkyl, or aryl moieties, and X is a halogen, usually Cl. Specific examples of hydrophobizing agents include, but are not limited to, trimethylchlorosilane (TMCS), triethylchlorosilane (TECS), triphenylchlorosilane (TPCS), dimethylchlorosilane (DMCS), dimethyldichlorosilane (DMDCS), and the like. Hydrophobizing agents can also be of the formula: Y(R3M)2, where M is a metal, Y is a bridging group such as NH or O, and R is a hydrophobic group such as CH3, CH2CH3, C6H6, or similar hydrophobic alkyl, cycloalkyl, or aryl moieties. Specific examples of such hydrophobizing agents include, but are not limited to, hexamethyldisilazane [HMDZ] and hexamethyldisiloxane [HMDSO]. Hydrophobizing agents may further include the following compounds: RNMV4-N, where V is a reactive or leaving group other than halogen. Specific examples of such hydrophobizing agents include, but are not limited to, vinyltriethoxysilane and vinyltrimethoxysilane.
[0114] The hydrophobic treatment of the present disclosure may also be performed during liquid removal, exchange, or drying of the gel. In specific embodiments, the hydrophobic treatment may be performed in a supercritical fluid environment (such as, but not limited to, supercritical carbon dioxide) and may be combined with a drying or extraction step.
[0115] Organic aerogel Organic aerogels are generally formed from carbon-based polymer precursors. Such polymeric materials include, but are not limited to, resorcinol formaldehyde (RF), polyimides, polyacrylates, polymethylmethacrylates, acrylate oligomers, polyoxyalkylenes, polyurethanes, polyphenols, polybutadians, trialkoxysilyl-terminated polydimethylsiloxanes, polystyrenes, polyacrylonitriles, polyfurfural, melamine formaldehyde, cresol formaldehyde, phenol furfural, polyethers, polyols, polyisocyanates, polyhydroxybenzenes, polyvinyl alcohol dialdehydes, polycyanurates, polyacrylamides, various epoxies, agar, agarose, chitosan, and combinations thereof. As an example, organic RF aerogels are generally made from the sol-gel polymerization of resorcinol or melamine with formaldehyde under alkaline conditions.
[0116] Organic / inorganic hybrid aerogel Organic / inorganic hybrid aerogels consist primarily of organically modified silica ("ormosil") aerogels. These ormosil materials contain organic components covalently bonded to a silica network. Ormosils are typically formed by hydrolysis and condensation of organically modified silanes, R--Si(OX)3, with conventional alkoxide precursors Y(OX)4. In these formulas, X can represent, for example, CH3, C2H5, C3H7, C4H9, Y can represent, for example, Si, Ti, Zr, or Al, and R can be any organic fragment, such as methyl, ethyl, propyl, butyl, isopropyl, methacrylate, acrylate, vinyl, epoxide, etc. The organic components of ormosil aerogels can also be dispersed throughout or chemically bonded to the silica network.
[0117] In certain embodiments, the aerogels of the present disclosure are inorganic silica aerogels formed primarily from prepolymerized silica precursors, such as oligomers, or hydrolyzed silicate esters formed from silicon alkoxides in alcohol solvents. In certain embodiments, such prepolymerized silica precursors or hydrolyzed silicate esters may be formed in situ from other precursors or silicate esters, such as alkoxysilanes or water glasses. However, the present disclosure as a whole may be practiced with any other aerogel compositions known to those skilled in the art and is not limited to any one precursor material, or amalgam mixtures of precursor materials.
[0118] Macropores As explained above, aerogel compositions according to embodiments of the present disclosure may include an aerogel skeleton that includes macropores. Without being bound to any particular theory of operation, the presence of macropores within the aerogel skeleton may allow for compression of the aerogel composition, e.g., a reinforced aerogel composition, while maintaining or even improving thermal properties, e.g., reducing thermal conductivity. For example, the macropores may deform, shatter, or otherwise reduce in size upon compression of the composition, thereby allowing the thickness of the composition to be reduced when subjected to a load. However, as the macropores deform, they effectively become smaller pores. As a result, as the macropores deform, the paths for heat transfer within the aerogel skeleton may become more tortuous, thereby improving thermal properties, e.g., reducing thermal conductivity. Within the context of the present disclosure, "mesopores" are pores with an average pore size ranging from about 2 nm to about 50 nm. Aerogel skeletons are generally mesoporous (i.e., primarily including pores with average diameters ranging from about 2 nm to about 50 nm). In certain embodiments, the aerogel skeleton of the aerogel composition of the present disclosure may include macropores. Within the context of the present disclosure, "macropores" are pores having an average pore size greater than about 50 nm. The aerogel skeleton may include both macropores and mesopores. For example, at least 10% of the pore volume of the aerogel skeleton may be comprised of macropores, at least 5% of the pore volume of the aerogel skeleton may be comprised of macropores, at least 75% of the pore volume of the aerogel skeleton may be comprised of macropores, at least 95% of the pore volume of the aerogel skeleton may be comprised of macropores, or 100% of the pore volume of the aerogel skeleton may be comprised of macropores. In some particular embodiments, the aerogel skeleton may be a macroporous aerogel skeleton, such that a majority of its pore volume is comprised of macropores. In some cases, the macroporous aerogel skeleton may also include micropores and / or mesopores. In some embodiments, the average pore size (diameter) of the pores in the aerogel framework is greater than 50 nm, and can be between 50 nm and 5000 nm, between 250 nm and 2000 nm, between 500 nm and 2000 nm, between 500 nm and 1400 nm, or between 1200 nm.In certain embodiments, the average pore size diameter may be greater than 50 nm, between 50 nm and 1000 nm, preferably between 100 nm and 800 nm, and more preferably between 250 nm and 750 nm.
[0119] Homogeneous and heterogeneous pore size distribution
[0120] In some embodiments, the variation in pore size within the aerogel framework can be homogeneously distributed throughout the aerogel framework, e.g., the average pore size can be substantially the same throughout the aerogel framework.
[0121] In other embodiments, the pore size variation within the aerogel skeleton can be distributed heterogeneously throughout the aerogel skeleton. For example, the average pore size can be different in certain regions of the aerogel skeleton. In some exemplary embodiments, the average pore size can be greater at the top surface, the bottom surface, or both the top and bottom surface regions of the aerogel skeleton. For example, the macropores can be distributed within the composition such that the ratio of macropores to mesopores is greater at the top surface than the bottom surface, greater at the bottom surface than the top surface, or greater at both the top and bottom surfaces than the intermediate region between the top and bottom surfaces. As another example, the macropores can be distributed within the composition such that the ratio of macropores to mesopores is greater near the top surface than the bottom surface, greater near the bottom surface than the top surface, or greater near both the top and bottom surfaces than the intermediate region between the top and bottom surfaces. In other embodiments, the average pore size can be greater in the intermediate region between the top and bottom surfaces of the aerogel skeleton.
[0122] Macropore formation Macropores can be formed during the formation of the aerogel composition. For example, macropore formation can be induced in a gel precursor material during its transition to a gel composition. In some embodiments, macropore formation can be induced, for example, by inducing spinodal decomposition of a gel precursor solution. As another example, macropore formation can be induced by the addition of one or more blowing agents.
[0123] Macropores present in the resulting aerogel framework can be created by selecting processing conditions that favor the formation of macropores relative to mesopores and / or micropores. The amount of macropores can be adjusted by implementing any one, any combination, or all of the following variables: The variables include: (1) the solvent used for polymerization, (2) the polymerization temperature, (3) the polymer molecular weight, (4) the molecular weight distribution, (5) the copolymer composition, (6) the amount of branching, (7) the amount of crosslinking, (8) the branching method, (9) the crosslinking method, (10) the method used to form the gel, (11) the type of catalyst used to form the gel, (12) the chemical composition of the catalyst used to form the gel, (13) the amount of catalyst used to form the gel, (14) the temperature of gel formation, (15) the type of gas flowing across the material during gel formation, (16) the flow rate of the gas flowing across the material during gel formation, (17) the atmospheric pressure during gel formation, (18) the removal of dissolved gas during gel formation, (19) the presence of solid additives to the resin during gel formation, (20) the time of the gel formation process, (21) the substrate used for gel formation, (22) the type of solvent or solvents used at each step of the solvent exchange process, and (23) the solvent or solvents used at each step of the solvent exchange process. (24) the composition of the solvent used at each step of the solvent exchange process, (25) the residence time of the part at each step of the solvent exchange process, (26) the flow rate of the solvent during the solvent exchange, (27) the type of solvent flow during the solvent exchange, (28) the agitation rate of the solvent during the solvent exchange, (29) the temperature used at each step of the solvent exchange process, (30) the ratio of the volume of the solvent to the volume of the part during the solvent exchange, (31) the drying method, (32) the temperature at each step of the drying process, (33) the pressure at each step of the drying process, (34) the composition of the gas used at each step of the drying process, (35) the rate of gas flow during each step of the drying process, (36) the temperature of the gas during each step of the drying process, (37) the temperature of the part during each step of the drying process, (38) the presence of an enclosure around the part during each step of the drying process, (39) the type of enclosure around the part being dried, and / or (40) the solvent used at each step of the drying process.The polyfunctional amine and diamine compounds are added separately or together in one or more portions as solids, and may be pure or dissolved in a suitable solvent. In another aspect, a method of making an aerogel may include the steps of: (a) providing a polyfunctional amine compound and at least one diamine compound in a solvent to form a solution; (b) providing at least one dianhydride compound to the solution of step (a) under conditions sufficient to form a branched polymer matrix solution, where the branched polymer matrix is solubilized in the solution; and (c) exposing the branched polymer matrix solution to conditions sufficient to form an aerogel having an open cell structure. Macropores present in the resulting aerogel framework may be formed in the manner described above. In a preferred, non-limiting aspect, the formation of macropores, as compared to the smaller mesopores and micropores, may be controlled primarily by controlling the polymer / solvent dynamics during gel formation.
[0124] As explained above, aerogel compositions according to embodiments of the present disclosure may include an aerogel skeleton and a reinforcing material, where at least a portion of the reinforcing material does not contain aerogel. For example, the aerogel skeleton may extend partially through the thickness of the reinforcing material. In such embodiments, portions of the reinforcing material, e.g., OCMF, fibers, or combinations thereof, may include aerogel material and portions may be free of aerogel. For example, in some embodiments, the aerogel extends through about 90% of the thickness of the reinforcing material, through a range of about 50% to about 90% of the thickness of the reinforcing material, through a range of about 10% to about 50% of the thickness of the reinforcing material, or through about 10% of the thickness of the reinforcing material.
[0125] Without being bound to any particular theory of operation, aerogel compositions in which at least a portion of the reinforcement material does not contain aerogel can provide desirable properties of compressibility, compressive resiliency, and compliance. For example, the properties of the reinforcement material can be selected to provide sufficient reinforcement and support thermal properties in the regions containing aerogel, and also to provide sufficient compressibility, compressive resiliency, and / or compliance in the regions free of aerogel. The aerogel-containing portion of the reinforced aerogel composition can provide a desired thermal conductivity, e.g., a thermal conductivity of less than about 25 mW / m*K, while the reinforced portion free of aerogel can provide or improve a desired physical property, e.g., a desired compressibility.
[0126] In some embodiments, reinforced aerogel compositions in which at least a portion of the reinforcing material does not contain aerogel can be formed using the methods disclosed herein, where the reinforcing material is combined with a sufficient amount of precursor solution to partially fill the reinforcing material with the precursor solution. For example, the volume of the precursor can be less than the volume of the reinforcing material, so that the precursor extends only partially through the reinforcing material. As explained above, when dried, the resulting reinforced aerogel composition includes an aerogel skeleton that extends through less than the entire thickness of the reinforcing material. In other embodiments, reinforced aerogel compositions in which at least a portion of the reinforcing material does not contain aerogel can be formed by removing a surface aerogel layer from the reinforced aerogel composition.
[0127] In some embodiments, reinforced aerogel compositions, in which at least a portion of the reinforcement does not contain aerogel, can be formed using a reinforcement that has the property of intermixing through the thickness of the reinforcement. For example, the reinforcement can include multiple layers, each layer having different properties, such as differences in average pore / cell size, material composition, closed cells, open cells, surface treatment, or combinations thereof. The multiple layers can be bonded to each other, for example, using an adhesive, by frame bonding, or by other suitable methods or mechanisms, such as those described herein. Different properties of the reinforcement can result in a change in the distribution of aerogel through the layers. For example, the open cell portion of the reinforcement can include an aerogel framework, while the closed cell portion remains substantially free of aerogel. Similarly, other material properties of the reinforcement or its layers can determine the distribution within the aerogel of the reinforcement, and thus within the reinforced aerogel composition.
[0128] In some exemplary embodiments, reinforced aerogel compositions can be formed using the methods disclosed herein, where at least a portion of the reinforcing material does not contain aerogel, and the properties of the reinforcing material, or the properties of a layer of the reinforcing material, control or influence the amount of precursor solution that fills the material or layer, e.g., during a coating process, to provide partial filling of the reinforcing material with the precursor solution. For example, one layer of the reinforcing material can have open cells and another layer of the reinforcing material can have closed cells. When a precursor solution is combined with such a reinforcing material, the gel precursor solution can infiltrate the open cells of the layer while not substantially infiltrating the closed cells of the other layer. When such a composition dries, the resulting reinforced aerogel composition can include one portion, e.g., a closed cell layer, that does not contain aerogel, while another portion, e.g., an open cell layer, contains aerogel.
[0129] In some embodiments, the additives disclosed herein (e.g., heat-absorbing additives, opacifying additives, fire-rated additives, or other additives) can be non-uniformly distributed within the reinforced aerogel composition. For example, the additive material can vary through the thickness of the aerogel composition or along the length and / or width of the aerogel composition. For example, the additive can accumulate on one side of the aerogel composition. In some embodiments, the additive material(s) can be collected in one layer of the aerogel composition or can be provided as a separate layer consisting essentially of the additive adjacent to or attached to the composition. For example, the thermal control member can include a layer consisting essentially of a heat-absorbing material, such as gypsum, baking soda, magnesia-based cement, etc. In further exemplary embodiments, the aerogel composition can also include at least one layer of an additional material, either within the composition or as a skin layer. For example, the layer can be a layer selected from the group consisting of a polymer sheet, a metal sheet, a fiber sheet, a highly oriented graphite material (e.g., a pyrolytic graphite sheet), and a fabric sheet. In some embodiments, the skin layer can be attached to the composition by an adhesive mechanism selected from the group consisting of, for example, aerosol adhesives, urethane adhesives, acrylate adhesives, hot melt adhesives, epoxies, rubber resin adhesives, polyurethane composite adhesives, and combinations thereof. In some embodiments, the skin layer can be attached to the composition by a non-adhesive mechanism, for example, by a mechanism selected from the group consisting of frame bonding, needling, stitching, sealing bags, rivets, buttons, clamps, wraps, braces, and combinations thereof. In some embodiments, the skin layer can be attached to the composition using any combination of the aforementioned adhesive and non-adhesive mechanisms.
[0130] Powder aerogel composition As described herein, an aerogel composition or composite may include materials that incorporate aerogel particulates, particles, granules, beads, or powders into a solid or semi-solid material, together with a binder such as an adhesive, a resin, a cement, a foam, a polymer, or similar solid or solidified material. For example, an aerogel composition may include a reinforcing material, aerogel particles, and optionally a binder. In an exemplary embodiment, a slurry may be provided that includes aerogel particles and at least one type of wetting agent. For example, the aerogel particles may be coated or wetted with at least one wetting agent, such as a surfactant or dispersant. The aerogel particles may be fully wetted, partially wetted (e.g., surface wet), or present in the slurry. Preferred wetting agents are capable of volatilization, allowing for proper recovery of the hydrophobicity of the hydrophobic aerogel particles. If the wetting agent remains on the surface of the aerogel particles, the remaining wetting agent may contribute to the overall thermal conductivity of the composite. Thus, preferred wetting agents are those that are removable, such as by volatilization with or without decomposition or other means. Generally, any wetting agent that is compatible with aerogel can be used.
[0131] Wetting Agent The wetting agent coated slurry or aerogel can be useful in a method to easily incorporate the hydrophobic aerogel into various materials such as other water-containing fluids, slurries, adhesives, binder materials, which can optionally be cured to form solid materials, fibers, metal fibers, discrete fibers, woven materials, nonwoven materials, needle punched nonwovens, batting, webs, mats, felts, and combinations thereof. Aerogel wetted with at least one wetting agent, or a slurry containing aerogel with at least one wetting agent, allows for easy incorporation and uniform distribution of the hydrophobic aerogel. In wet laid processes such as those described in U.S. Pat. Nos. 9,399,864, 8,021,583, 7,635,411, and 5,399,422 (each of which patents are incorporated herein by reference in their entirety), an aqueous slurry is used to disperse the aerogel particles, fibers, and other additives. The slurry can then be dewatered to form layers of aerogel particles, fibers, and additives, which can be dried and optionally calendared to produce an aerogel composite.
[0132] Aerogel particles and additives In other embodiments, the aerogel composition includes aerogel particles, at least one inorganic matrix material, and may optionally include fibers, auxiliary materials, additives, and additional inorganic binders. The inorganic matrix material may include, in some embodiments, a phyllosilicate, such as a naturally occurring phyllosilicate such as kaolin, clay, or bentonite, a synthetic phyllosilicate such as magadite or kenyaite, or mixtures thereof. The phyllosilicate may or may not be burned, for example, by drying the material and removing the water of crystallization. The inorganic matrix material may also include, in some embodiments, an inorganic binder, such as cement, lime, gypsum, or a suitable mixture thereof, combined with the phyllosilicate. The inorganic matrix material may also include other inorganic additives, such as fire-rated additives, opacifiers, or combinations thereof, as disclosed herein. Aerogel compositions comprising inorganic matrix materials and exemplary processes thereof are disclosed in U.S. Patent No. 6,143,400, U.S. Patent No. 6,083,619, each of which is incorporated herein by reference in its entirety. In some embodiments, the aerogel composition may include aerogel particles coated on or absorbed within a woven material, a nonwoven material, a needle punched nonwoven, a batting, a web, a mat, a felt, and combinations thereof. An adhesive binder may be included in the composition. It may also include additives such as fire-rated additives, opacifiers, or combinations thereof, as disclosed herein. Aerogel compositions coated on or absorbed into fabrics and exemplary processes thereof are disclosed in U.S. Patent Publication No. 2019 / 0264381 A1, each of which is incorporated herein by reference in its entirety.
[0133] As described herein, the aerogel composition can be laminated or faced to another material, such as a reinforcing layer of a facing material. In one embodiment, the present disclosure provides a multi-layer laminate including at least one base layer including a reinforced aerogel composition and at least one skin layer. In one embodiment, the skin layer includes a reinforcing material. In one embodiment, the reinforced aerogel composition is reinforced with a fiber reinforcement layer or an open cell foam reinforcement layer. In one embodiment, the present disclosure provides a multi-layer laminate including a base layer including a reinforced aerogel composition and at least two skin layers including a reinforcing material, the two skin layers being on opposite sides of the base layer. For example, a multi-layer aerogel laminate composition can be produced according to the methods and materials described in U.S. Patent Application Publication No. 2007 / 0173157.
[0134] The skin layer may include a material that helps provide unique characteristics to the final composite structure, such as improved flexibility or reduced surface dusting. The face material may be rigid or flexible. The face material may include a conductive layer or a reflective foil. For example, the face material may include a metallic or metallized material. The face material may include a nonwoven material. The skin layer may be disposed on a surface of the composite structure or on a surface of the reinforced aerogel composite forming the composite structure, e.g., a thermal control member. The skin layer may form a continuous coating or bag around the composite structure or around the reinforced aerogel composite forming the composite structure, e.g., a thermal control member. In some embodiments, a skin layer or multiple skin layers may encapsulate the composite structure or the reinforced aerogel composite forming the composite structure.
[0135] In one embodiment, the skin layer comprises a polymer sheet around the synthetic structure, more specifically a polymeric material including polyester, polyethylene, polyurethane, polypropylene, polyacrylonitrile, polyamide, aramid, more specifically a polymer such as polyethylene terephthalate, low density polyethylene, ethylene-propylene copolymers, poly(4-methylpentane), polytetrafluoroethylene, poly(l-butene), polystyrene, polyvinyl acetate, polyvinyl chloride, polyvinylidene chloride, polyvinyl fluoride, polyvinyl acrylonitrile, polymethyl methacrylate, polyoxymethylene, polyphenylene sulfone, cellulose triacetate, polycarbonate, polyethylene naphthalate, polycaprolactam, polyhexamethylene adipamide, polyundecanoamide, polyimide, or combinations thereof. In one embodiment, the polymer sheet comprises or consists essentially of an expanded polymer material, more specifically an expanded polymer material including PTFE (ePTFE), expanded polypropylene (ePP), expanded polyethylene (ePE), expanded polystyrene (ePS), or combinations thereof. In one preferred embodiment, the facing material consists essentially of an expanded polymer material. In one embodiment, the polymer sheet comprises or consists essentially of a microporous polymer material characterized by pore sizes ranging from 0.1 μm to 210 μm, 0.1 μm to 115 μm, 0.1 μm to 15 μm, or 0.1 μm to 0.6 μm.
[0136] In one embodiment, the skin layer material comprises or consists essentially of a fluoropolymer material. Within the context of this disclosure, the term "fluoropolymer" or "fluoropolymer material" refers to a material that primarily comprises polymeric fluorocarbons. Suitable fluoropolymer skin layer materials include, but are not limited to, polytetrafluoroethylene (PTFE), polyvinyl fluoride (PVF), polyvinylidene fluoride (PVDF), perfluoroalkoxy (PFA), fluorinated ethylene propylene (FEP), polychlorotrifluoroethylene (PCTFE), ethylene tetrafluoroethylene (ETFE), polyvinylidene fluoride (PVDF), ethylene chlorotrifluoroethylene (ECTFE), and combinations thereof, including microporous PTFE as described in U.S. Pat. No. 5,814,405, and expanded PTFE (ePTFE), such as Gore-Tex® (available from WL Gore). In one preferred embodiment, the face material consists essentially of a fluoropolymer material. In one preferred embodiment, the face material consists essentially of an expanded PTFE (ePTFE) material.
[0137] In one embodiment, the skin layer material comprises or consists essentially of a non-fluoropolymer material. Within the context of this disclosure, the terms "non-fluoropolymer" or "non-fluoropolymer material" refer to materials that do not contain fluoropolymer materials. Suitable non-fluoropolymer skin layer materials include, but are not limited to, aluminized Mylar, low density polyethylene such as Tyvek® (available from DuPont), rubber or rubber composites, nonwoven materials, elastic fibers such as spandex, nylon, lycra, or elastane, and combinations thereof. In one embodiment, the face material is a flexible face material.
[0138] In some embodiments, the skin layer materials can include automotive resins and polymers, such as materials that have a maximum use temperature of up to about 100° C., up to about 120° C., or up to about 150° C. For example, the skin layer materials can include acrylonitrile butadiene styrene (ABS), polycarbonate ABS, polypropylene, polyurethane, polystyrene, polyethylene, polycarbonate, polyimide, polyamide, PVC, or combinations thereof. For example, aerogel compositions and thermal control members according to embodiments disclosed herein can include a layer of automotive resin or automotive polymer, a metal or metallized layer, and an aerogel layer.
[0139] The skin layer can be attached to the base layer by using an adhesive suitable for securing the inorganic or organic facing material to the reinforcement of the base layer. Examples of adhesives that can be used in the present disclosure include, but are not limited to, cement-based adhesives, sodium silicate, latex, pressure sensitive adhesives, silicone, polystyrene, aerosol-based adhesives, urethane, acrylate-based adhesives, hot melt bonding systems, bonding systems available from 3M, epoxy resins, rubber resin adhesives, mixtures of polyurethane-based adhesives such as those described in U.S. Pat. No. 4,532,316.
[0140] The skin layer can also be attached to the base layer by using a suitable non-adhesive or technique to secure the inorganic or organic surface material to the support of the base layer. Examples of non-adhesive materials or techniques that can be used in the present disclosure include, but are not limited to, heat sealing, ultrasonic stitching, RF sealing, stitching or threading, needling, sealed bags, rivets or buttons, clamps, wraps, or other non-adhesive lamination materials.
[0141] The skin layer can be attached to the base layer at any stage of the production of the aerogel composite. In one embodiment, the skin layer is attached to the base layer after injecting the sol-gel solution into the base reinforcement but before gelling. In another embodiment, the skin layer is attached to the base layer after injecting the sol-gel solution into the base reinforcement and after subsequent gelling but before the gel material degrades or dries. In yet another embodiment, the skin layer is attached to the base layer after the gel material ages or dries. In a preferred embodiment, the skin layer is attached to the base layer before injecting the sol-gel solution into the base reinforcement. The skin layer can be solid and impermeable to fluids. The skin layer can be porous and permeable to fluids. In a preferred embodiment, the skin layer is porous and permeable to fluids, including pores or holes with a diameter large enough to allow the fluid to diffuse through the face material. In another preferred embodiment, the skin layer is attached to the base reinforcement prior to injecting the sol-gel solution into the base reinforcement, the skin layer being porous and containing pores or holes with a diameter large enough to allow fluid to permeate and to diffuse through the facing material. In yet another preferred embodiment, the skin layer is attached to the open cell foam reinforcement prior to injecting the sol-gel solution into the foam reinforcement, the skin layer being porous and containing pores or holes with a diameter large enough to allow fluid to permeate and to diffuse through the facing material.
[0142] Opacifying Agent The aerogel composition may include an opacifier to reduce the radiative component of heat transfer. At any time prior to gel formation, an opaque compound or precursor thereof may be dispersed in the mixture containing the gel precursor. Examples of opaque compounds include, but are not limited to, boron carbide (B4C), diatomaceous earth, manganese ferrite, MnO, NiO, SnO, Ag2O, Bi2O3, carbon black, graphite, titanium oxide, titanium iron oxide, aluminum oxide, zirconium silicate, zirconium oxide, iron (II) oxide, iron (III) oxide, manganese dioxide, titanium iron oxide (ilmenite), chromium oxide, carbides (such as SiC, TiC, or WC-ceramic), or mixtures thereof. Examples of precursors of opaque compounds include, but are not limited to, TiOSO4 or TiOCl2. In some embodiments, for opaque compounds used as additives, silicon carbide whiskers or fibers may be excluded. When the aerogel composition is intended for use in an electrical device, for example, in a battery as a barrier layer, or other related applications, the composition including the opacifier can desirably possess high dielectric strength with high capacity and high surface resistivity. In such embodiments, the carbon additive used as the opacifier can be non-conductive or can be modified to reduce electrical conductivity. For example, the opacifier can be surface oxidized to reduce electrical conductivity. In some embodiments, a carbon additive with inherent electrical conductivity can be used as an opacifier in an aerogel composition intended for use in an electrical device. In such embodiments, the conductive carbon additive can be used at a concentration below the percolation threshold to provide the composition with suitable dielectric strength for use in an electrical device.
[0143] Fire Grade Additives The aerogel composition may include one or more fire-rated additives. Within the context of this disclosure, the term "fire-rated additive" refers to a material that provides an endothermic effect in relation to the response to fire and that is miscible in the aerogel composition. Furthermore, in certain embodiments, the fire-rated additive has an onset temperature of endothermic decomposition (ED) that is no more than 100° C. relative to the onset temperature of thermal decomposition (Td) of the aerogel composition in which the fire-rated additive is present, and in certain embodiments, an onset temperature of ED that is no more than 50° C. relative to the Td of the aerogel composition in which the fire-rated additive is present. In other words, the ED of the fire-rated additive is (T d -50℃)~(T d +100℃).
number
[0144] Prior to, simultaneously with, or even subsequent to mixing or blending with the sol (e.g., silica sol prepared from alkyl silicates or water glass in various ways as understood in the art), the fire-rated additive can be mixed with or otherwise dispersed in a medium including ethanol and, optionally, up to 10% water by volume. The mixture can be mixed and / or stirred as necessary to achieve a substantially uniform dispersion of the additive in the medium. Without being bound by theory, the hydrated forms of the clays and other fire-rated additives described above can be utilized to provide additional endothermic effects. For example, halloysite clay (a product commercially available from Applied Minerals, Inc. under the trade name DRAGONITE or simply Halloysite from Imerys), kaolinite clay, is an aluminum silicate clay that, in its hydrated form, provides an endothermic effect by releasing water of hydration (gas dilution) at elevated temperatures. As another example, carbon in its hydrated form can release carbon dioxide at elevated temperatures or at elevated temperatures.
[0145] Within the context of this disclosure, the term "heat of dehydration" refers to the amount of heat required to evaporate water (and dihydroxylation, if applicable) from a material in its hydrated form when not exposed to elevated temperature. Heat of dehydration is generally expressed on a per unit weight basis.
[0146] In certain embodiments, the fire grade additives of the present disclosure have an onset temperature of thermal decomposition of about 100° C. or higher, about 130° C. or higher, about 200° C. or higher, about 230° C. or higher, about 240° C. or higher, about 330° C. or higher, 350° C. or higher, about 400° C. or higher, about 415° C. or higher, about 425° C. or higher, about 450° C. or higher, about 500° C. or higher, about 550° C. or higher, about 600° C. or higher, about 650° C. or higher, about 700° C. or higher, about 750° C. or higher, about 800° C. or higher, or a range between any two of these values. In certain embodiments, the fire grade additives of the present disclosure have an onset temperature of thermal decomposition of about 440° C. or 570° C. In certain embodiments, the fire grade additives of the present disclosure have an onset temperature of thermal decomposition that is no greater than about 50° C., no greater than about 40° C., no greater than about 30° C., no greater than about 20° C., no greater than about 10° C., no greater than about 5° C., or in a range between any two of these values, relative to the Td of the aerogel composition (without the fire grade additive) into which the fire grade additive is incorporated.
[0147] Fire grade additives of the present disclosure include, but are not limited to, the following clay materials: phyllosilicate clays (such as illite), kaolin or kaolinite (aluminum silicate; Al2Si2O5(OH)4), metakaolin, halloysite (aluminum silicate; Al2Si2O5(OH)4), endellite (aluminum silicate; Al2Si2O5(OH)4), mica (silica mineral), diaspore (aluminum oxide hydroxide; α-AlO(OH)), gibbsite (aluminum hydroxide), boehmite (aluminum oxide hydroxide; γ-AlO(OH)), montmorillonite, beidellite, pyrophyllite (aluminum silicate; Al2Si4O10(OH)2), nontronite, brabysite, smectite, levalierite, lectrais, hexafluorophosphate ... Examples of suitable clay materials include gypsum, celadonite, attapulgite, chloropearl, volkonskoite, allophane, racewinite, dillnite, sebelite, myrosite, coryllite, simolite, newtonite, sodium bicarbonate (NaHCO3), magnesium hydroxide (or magnesium dihydroxide, "MDH"), alumina trihydrate ("ATH"), gypsum (calcium sulfate dihydrate; CaSO4·2H2O), baringtonite (MgCO3·2H2O), nesquehonite (MgCO3·3H2O), lansfordite (MgCO3·5H2O), hydromagnesium carbonate (hydrated magnesium carbonate; Mg5(CO3)4(OH)2·4H2O), and other carbons such as, but not limited to, dolomite and lithium carbon. Certain embodiments of the present disclosure use clay materials having at least a partial layered structure, among others. In certain embodiments of the present disclosure, the clay material as a fire-rated additive in the aerogel composition has at least some water, such as in a hydrated form. The additive may be in a hydrated crystalline form or may become hydrated during the manufacture / processing of the composition of the present disclosure. In certain embodiments, the fire-rated additive also includes a low melting additive that absorbs heat without changing in chemical composition. Examples of this class include low melting glasses, such as inert glass beads. Other additives that may be useful in the compositions of the present disclosure include, but are not limited to, wollastonite (calcium silicate) and titanium dioxide (TiO2).In certain embodiments, other additives may include infrared opacifiers, such as, but not limited to, titanium dioxide or silicon carbide, low melting point glass frits, ceramifiers, such as, but not limited to, calcium silicate, or char formers, such as, but not limited to, phosphates and sulfates. In certain embodiments, additives may require special processing considerations, such as techniques to ensure that the additives are distributed evenly and do not aggregate in large amounts that would cause changes in product performance. Processing techniques may include additional static and dynamic mixers, stabilizers, adjustments to process conditions, and others known in the art.
[0148] Amount of additive The amount of additive in the aerogel compositions disclosed herein can depend on the desired properties of the composition. The amount of additive used during formulation and processing of the sol-gel composition is generally referred to as a weight percentage relative to the silica content of the sol. The amount of additive in the sol can vary from about 5 wt% to about 70 wt% by weight relative to the silica content. In certain embodiments, the amount of additive in the sol is 10 wt% to 60 wt% relative to the silica content, and in certain preferred embodiments, the amount is 20 wt% to 40 wt% relative to the silica content. In exemplary embodiments, the amount of additive in the sol relative to the silica content ranges from about 5% to about 20%, about 10% to about 20%, about 10% to about 30%, about 10% to about 20%, about 30 wt% to about 50 wt%, about 35 wt% to about 45 wt%, or about 35 wt% to about 40 wt% relative to the silica content. In some embodiments, the amount of additive in the sol is at least about 10 wt% based on the silica content, or about 10 wt% based on the silica content. In some embodiments, the amount of additive ranges from about 5 wt% to about 15 wt% based on the silica content. In certain embodiments, the additive can be of more than one type. One or more fire-rated additives can also be present in the final aerogel composition. In some preferred embodiments including an aluminum silicate fire-rated additive, the additive is present in the aerogel composition at about 60-70 wt% based on the silica content. For example, in some preferred embodiments including an aluminum silicate fire-rated additive such as kaolin, or a combination of an aluminum silicate fire-rated additive such as kaolin and alumina trihydrate ("ATH"), the total amount of additive present in the aerogel composition is about 30-40 wt% based on the silica content. As another example, in some preferred embodiments where the additive comprises silicon carbide, the total amount of additive present in the aerogel composition is about 30-40 wt%, e.g., 35 wt%, based on the silica content. As another example, in some preferred embodiments where the additive comprises silicon carbide, the total amount of additive present in the aerogel composition is about 5-15 wt%, e.g., 10 wt%, based on the silica content.
[0149] When referring to the final reinforced aerogel composition, the amount of additive is generally referred to as a weight percent of the final reinforced aerogel composition. The amount of additive in the final reinforced aerogel composition can vary from about 1% to about 50%, from about 1% to about 25%, or from about 10% to about 25% by weight of the reinforced aerogel composition. In exemplary embodiments, the amount of additive in the final reinforced aerogel composition ranges from about 10% to about 20% by weight of the reinforced aerogel composition. In exemplary embodiments, the amount of additive in the final reinforced aerogel composition, as a weight percent of the composition, is about 1%, about 2% about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, or a range between any of the aforementioned percentages. In certain embodiments, the amount of additive in the final reinforced aerogel composition is about 15% by weight of the reinforced aerogel composition. In certain embodiments, the amount of additive in the final reinforced aerogel composition is about 13% by weight of the reinforced aerogel composition. For example, in some preferred embodiments including additives such as silicon carbide, the total amount of additive present in the aerogel composition is about 10-20 wt.%, e.g., about 15 wt.%, by weight of the reinforced aerogel composition. As another example, in some preferred embodiments including additives such as silicon carbide, the total amount of additive present in the aerogel composition is about 3-5 wt.%, e.g., about 4 wt.%, by weight of the reinforced aerogel composition.
[0150] Onset temperature of thermal decomposition of fire-rated additives In certain embodiments, fire-rated additives can be classified or grouped based on their onset temperature of thermal decomposition. For example, fire-rated additives can be classified or grouped as having an onset temperature of thermal decomposition less than about 200° C., less than about 400° C., or greater than about 400° C. For example, additives having an onset temperature of thermal decomposition less than about 200° C. include baking soda (NaHCO3), nesquehonite (MgCO3·3H2O), and gypsum (calcium sulfate dihydrate; CaSO4·2H2O). As another example, additives having an onset temperature of thermal decomposition less than about 400° C. include alumina trihydrate ("ATH"), hydromagnesium carbonate (hydrated magnesium carbon; Mg5(CO3)4(OH)2·4H2O), and magnesium hydroxide (or magnesium dihydroxide, "MDH"). As another example, additives having an onset temperature of thermal decomposition less than about 400° C. include halloysite (aluminum silicate; Al2Si2O5(OH)4), kaolin or kaolinite (aluminum silicate; Al2Si2O5(OH)4), boehmite (aluminum oxide hydroxide; γ-AlO(OH)), or a high temperature phase change material (PCM).
[0151] In certain embodiments of the present disclosure, the clay material, e.g., an aluminosilicate clay such as halloysite or kaolinite, is in a dehydrated form, e.g., metahalloysite or metakaolin, as an additive in the aerogel composition. Other additives that may be useful in the compositions of the present disclosure include, but are not limited to, wollastonite (calcium silicate) and titanium dioxide (TiO2). In certain embodiments, other additives may include infrared opacifiers, such as, but not limited to, titanium dioxide or silicon carbide, low melting glass frits, ceramifiers, such as calcium silicate, or char formers, such as, but not limited to, phosphates and sulfates. In certain embodiments, additives may require special processing considerations, such as techniques to ensure that the additives are distributed uniformly and do not aggregate in large amounts that would cause changes in product performance. Processing techniques may include additional static and dynamic mixers, stabilizers, adjustments in process conditions, and others known in the art. One or more fire-rated additives may also be present in the final aerogel composition.
[0152] In certain embodiments, the inclusion of additives, for example, aluminosilicate clay-based materials such as halloysite or kaolin, in the aerogel materials and compositions of the present disclosure may result in improved high temperature shrinkage properties. An exemplary test method for high temperature shrinkage is the "Standard Test Method for Linear Shrinkage of Preformed High-Temperature Thermal Insulation Subjected to Soaking Heat" (ASTM C356, ASTM International, West Conshohocken, PA). In such a test, the material, referred to as "heat soaked," is exposed to temperatures greater than 1000°C for a period of up to 60 minutes. In certain exemplary embodiments, the aerogel materials or compositions of the present disclosure may have a high temperature shrinkage, i.e., any combination of linear shrinkage, width shrinkage, thickness shrinkage, or dimensional shrinkage, of about 20% or less, about 15% or less, about 10% or less, about 6% or less, about 5% or less, 4% or less, 3% or less, 2% or less, 1% or less, or a range between any two of these values.
[0153] In some exemplary embodiments, certain basic catalysts used to catalyze the precursor reaction may result in trace levels of other alkali metals in the aerogel composition. Trace levels of an aerogel material, such as 100-500 ppm of alkali, e.g., sodium or potassium, may adversely affect high temperature shrinkage and thermal durability. However, without being bound to any particular mechanism or theory, an aluminosilicate clay-based material, such as halloysite or kaolin, may sequester the released alkali, e.g., sodium or potassium, thereby reducing or eliminating the effect of the alkali on shrinkage and thermal durability. In certain embodiments of the present disclosure, the aluminosilicate clay material is in a dehydrated form, such as metahalloysite or metakaolin. For example, an aerogel material or composition that includes an amount of metakaolin or metahalloysite greater than about 0.5 wt% relative to the silica content may significantly reduce thermal shrinkage and thermal durability. In an exemplary embodiment, the aerogel material or composition may include an amount of metakaolin or metahalloysite in the range of about 0.5 wt% to about 3.0 wt% relative to the silica content.
[0154] Encapsulation layer or encapsulation material layer In some embodiments, the core of the multilayer material disclosed herein or the multilayer material may be encapsulated by an encapsulation layer. For example, the encapsulation layer may include a layer or layers of material surrounding the multilayer material and / or a coating of material surrounding the multilayer material and / or the core of the multilayer material. For example, the encapsulation layer may include a thin film, layer, envelope, or coating. The encapsulation member may be made of any material suitable for enclosing the composite structure or the reinforced aerogel composite forming the composite structure. For example, the encapsulation member may reduce or eliminate the generation of dust or particulate material that falls off the composite structure. The encapsulation material layer may be selected from a polymer, an elastomer, or a combination thereof. Examples of suitable polymers such as polyethylene terephthalate (PET), polyethylene (PE), polyimide (PI), rubber, and nylon have very low thermal conductivity (less than 1 W / m) that has the effect of reducing the thermal conductivity of the planar surface throughout the system. In one embodiment, the encapsulation layer includes a polyethylene terephthalate layer.
[0155] The encapsulation layer may include at least one vent that allows air to flow in and out of the panel. The encapsulation member may include at least one filter that filters particulate matter. In an exemplary embodiment, the encapsulation layer includes a vent that allows air to flow in and out of the panel and a particulate filter over the vent that keeps the particulate matter within the encapsulation member. In another embodiment, the encapsulation layer includes an edge seal that includes at least one vent and at least one particulate filter. In a further embodiment, the encapsulation layer includes an edge seal that includes at least one vent and at least one particulate filter, where the vent in the edge seal allows air to flow in and out of the encapsulation member edge and the filter captures and retains particulate matter in the airflow to prevent contamination of the air outside the encapsulation layer by the particulate matter.
[0156] Thermal Capacitance Layer In exemplary embodiments, the multilayer material may include a material or layer of material that provides thermal capacitance (i.e., a heat capacity material), e.g., a material having a specific heat capacity of at least about 0.2 J / (g·°C). In some embodiments, the material that provides thermal capacitance has a specific heat capacity of at least about 0.5 J / (g·°C). For example, the material that provides thermal capacitance may include a metal, such as aluminum, titanium, nickel, steel, iron, or combinations thereof. In some embodiments, the multilayer material may include a layer or coating of a material that provides thermal capacitance. In some embodiments, the multilayer material may include particles of a material that provides thermal capacitance disposed within a layer of the multilayer material, e.g., within a layer of the aerogel composition. In certain embodiments, the multilayer material may include at least one layer of a material that provides thermal capacitance disposed adjacent to the aerogel composition. In certain embodiments, the multilayer material may include at least one layer of a material that provides thermal capacitance disposed between at least two of the layers of the aerogel composition. In exemplary embodiments, the multilayer material may include both thermally conductive and heat capacity materials.
[0157] For example, the multi-layer material may include a material that provides both thermal capacitance and thermal conductivity, such as a metal, such as aluminum, titanium, nickel, steel, iron, or a combination thereof. As another example, the multi-layer material may include one or more different materials, or layers of materials, each of which provides either thermal capacitance, thermal conductivity, or a combination thereof, such as a layer including a metal and a layer including a thermally conductive polymer. Preferably, the thermally conductive layer has a melting temperature of at least 300°C, more preferably at least 600°C, even more preferably at least 1000°C, and even more preferably at least 1500°C.
[0158] In some embodiments, the heat capacity material can be selected from a phase change material. It can be appreciated that phase change materials are suitable for a variety of applications in energy storage systems, and that the material should not only have a relatively high thermal capacitance during a phase change, but also be relatively low cost and self-supporting, i.e., not require any sealing or special containment over the operating temperature range of the device, e.g., the packaged battery module. Additional desirable properties for energy storage applications include high thermal conductivity to quickly transport heat away from heat generating components, and the ability to customize the temperature at which the phase change occurs.
[0159] In some embodiments, the heat capacity material has a thermal conductivity along an in-plane dimension of at least about 200 mW / m·K.
[0160] Thermal Conductive Layer It has been discovered that the thermally conductive layers disclosed herein exhibit a significantly increased ability to rapidly dissipate heat throughout the multi-layer material xy plane, further improving durability under high thermal loads. Examples of high thermal conductivity materials include carbon fiber, graphite, silicon carbide, metals, including but not limited to copper, stainless steel, aluminum, etc., as well as combinations thereof.
[0161] In an exemplary embodiment, the multi-layer material may include a layer of a thermally conductive material or material that provides thermal conductivity. The thermally conductive layer of the present disclosure helps dissipate heat away from localized heat loads within the battery module or battery pack. For example, the thermally conductive layer may have a thermal conductivity of at least about 200 mW / m·K along an in-plane dimension. The thermally conductive material may include at least one layer including a metal, carbon, a conductive polymer, or a combination thereof.
[0162] In some embodiments of the above aspects, the multilayer material may include one or more thermally conductive layers, i.e., the multilayer material has a thermal conductivity greater than 50 W / mK, more preferably greater than 100 W / mK, and even more preferably greater than 200 W / mK (all values measured at 25° C.). For example, the multilayer material may include at least one layer including a thermally conductive material, e.g., a layer including a metal, carbon, a thermally conductive polymer, or a combination thereof. When used in connection with these embodiments, a thermally conductive material refers to a material having a thermal conductivity greater than that of an insulating material, e.g., an aerogel composition. In certain embodiments, the thermally conductive material has a thermal conductivity greater than that of the aerogel composition by at least about one order of magnitude. In some embodiments, the multilayer material may include multiple layers of the aerogel composition. In certain embodiments, the multilayer material may include at least one layer of a conductive material disposed adjacent to the aerogel composition. In certain embodiments, the multilayer material may include at least one layer of a conductive material disposed between at least two of the multiple layers of the aerogel composition. In some embodiments, the multi-layer material can include particles of a conductive material disposed within a layer of the multi-layer material, for example within a layer of an aerogel composition.
[0163] To aid in the distribution and removal of heat, in at least one embodiment, the thermally conductive layer is coupled to a heat sink. It is recognized that there are different techniques for coupling the heat sink to the thermally conductive layer, just as there are various types and configurations of heat sinks, and the present disclosure is not limited to the use of any one type of heat sink / coupling technique. For example, at least one thermally conductive layer of the multilayer material disclosed herein can be in thermal communication with an element of the cooling system of the battery module or battery pack, such as a cooling plate or cooling channel of the cooling system. As another example, at least one thermally conductive layer of the multilayer material disclosed herein can be in thermal communication with other elements of the battery pack, battery module, or battery system that can act as a heat sink, such as a wall of the pack, module, or system, or can be in thermal communication with other elements of the multilayer material disposed between the battery cells. As described in more detail herein, thermal communication between the thermally conductive layer of the multilayer material and a heat sink element in the battery system can enable the removal of excess heat from a cell or cells adjacent to the multilayer material to a heat sink, thereby reducing the impact, severity, or propagation of a thermal event that can generate excess heat, for example.
[0164] Preferably, the thermally conductive layer has a melting temperature of at least 300°C, more preferably at least 600°C, even more preferably at least 1000°C, and even more preferably at least 1500°C.
[0165] The thickness of the thermally conductive layer may depend on a variety of factors, including the composition, the properties of other elements of the multilayer, such as the compression pad, the number of thermal conductors included in the multilayer material, and the composition. Functionally, the thermally conductive layer should be thick enough to provide the desired in-plane thermal conductivity.
[0166] In some embodiments, the thermally conductive material, e.g., pyrolytic graphite sheet (PGS), may have a thickness of about 0.010 mm, 0.025 mm, 0.05 mm, 0.07 mm, 0.10 mm, or a range between any two of these values, and an in-plane thermal conductivity in the range of about 600 to about 1950 W / mK. In some embodiments, the thermally conductive material, e.g., a metal plate, may have a thickness of about 0.05 mm, about 0.07 mm, about 0.10 mm, about 0.20 mm, about 0.25 mm, about 0.30 mm, about 0.5 mm, about 0.75 mm, about 1 mm, about 1.5 mm, about 2 mm, about 3 mm, about 4 mm, about 5 mm, or a range between any two of these values.
[0167] In some embodiments, the thermally conductive material can be selected from a phase change material.
[0168] In some embodiments, thermal paste can be used between layers of the multi-layer material to ensure uniform and consistent thermal conduction between such layers. As used herein, thermal paste refers to various materials also known as thermal compounds, thermal greases, thermal interface materials (TIMs), thermal gels, thermal pastes, heat sink compounds, and heat sink pastes. For example, a layer of thermal paste can be disposed between the aerogel composition and any other layer. The other layers can include a layer or layers containing a thermally conductive or heat capacity material, a skin layer or skin layers, or an encapsulation layer, etc.
[0169] Sacrificial Material Layer In exemplary embodiments, the multilayer material may include a sacrificial material or a layer of a sacrificial material. Within the context of the present disclosure, the term "sacrificial material" or "sacrificial layer" refers to a material or layer that is intended to be sacrificed or at least partially removed in response to mechanical, thermal, chemical, and / or electromagnetic conditions to which the layer is subjected. For example, the sacrificial material or sacrificial layer may decompose when exposed to elevated temperatures, such as temperatures that occur before or during a thermal runaway event in a battery. In some embodiments, the sacrificial material layer may be disposed on an exterior surface, for example, on the exterior surface of a core portion of the multilayer material, or on an exterior surface of the multilayer material, e.g., on the exterior surface of the multilayer material.
[0170] In an exemplary embodiment, the sacrificial material or layer of the present disclosure may include a compressible pad having a compression modulus of about 1 MPa, about 2 MPa, about 3 MPa, about 4 MPa, about 5 MPa, about 6 MPa, about 7 MPa, about 8 MPa, about 9 MPa, about 10 MPa, about 11 MPa, about 12 MPa, or a range between any two of these values. The sacrificial material layer may be selected from the group consisting of siloxane, polyolefin, polyurethane, phenolic, melamine, cellulose acetate, and polystyrene. In some cases, the material layer is in the form of a foam. In some embodiments, the compressible pad or foam may wear down due to exposure to mechanical loads (such as being subjected to cyclic loading). In some embodiments, the compressible pad or foam decomposes after exposure to abnormal mechanical, chemical, and / or thermal events.
[0171] In some embodiments, the onset temperature of chemical decomposition of the sacrificial material layer ranges from about 200°C to about 400°C.
[0172] Suitable foams for use as compressible pads in the embodiments disclosed herein have a density of about 1.0 g / cc or less, about 0.90 g / cc or less, about about 0.80 g / cc or less, about 0.70 g / cc or less, about 0.60 g / cc or less, about 0.50 g / cc or less, about 0.40 g / cc or less, about 0.30 g / cc or less, about 0.20 g / cc or less, about 0.16 g / cc, about 0.10 g / cc or less, about 0.08 g / cc or less, or a range between any two of these values, and / or a void volume content of at least about 20 to about 99%, specifically a void volume content of about 30% or more, based on the total volume of the foam. In an exemplary embodiment, the foam has a density of about 0.08 g / cc to about 0.50 g / cc, a compression force deflection (CFD) of 25% at about 27 kPa to about 55 kPa, and a compression force set at about 70° C. of less than about 10%, specifically less than 5%. CFD is measured by calculating the force in kPa required to compress the sample to 25% of its original thickness according to ASTM D1056.
[0173] The polymer used in the foam can be selected from various types of thermoplastics, mixtures of thermoplastics, or thermosets. Examples of thermoplastics that can be used include polyacetal, polyacrylic, styrene acrylonitrile, polyolefin, acrylonitrile-butadiene-styrene, polycarbonate, polystyrene, polyethylene terephthalate, polybutylene terephthalate, polyamide (such as, but not limited to, nylon 6, nylon 6,6, nylon 6,10, nylon 6,12, nylon 11, or nylon 12), polyamideimide, polyarylate, polyurethane, ethylene propylene rubber (EPR), polyarylsulfone, polyethersulfone, polyphenylene sulfide, polyvinyl chloride, polysulfone, polyetherimide, polytetrafluoroethylene, fluorinated ethylene propylene, polychlorotrifluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyether ketone, polyether ether ketone, polyether ketone ketone bodies, and the like, or a combination comprising at least one of the aforementioned thermoplastics.
[0174] Examples of blends of thermoplastic resins that can be used in the polymer foam include acrylonitrile-butadiene-styrene / nylon, polycarbonate / acrylonitrile-butadiene-styrene, acrylonitrile-butadiene-styrene / polyvinyl chloride, polyphenylene ether / polystyrene, polyphenylene ether / nylon, polysulfone / acrylonitrile-butadiene-styrene, polycarbonate / thermoplastic urethane, polycarbonate / polyethylene terephthalate, polycarbonate / polybutylene terephthalate, thermoplastic elastomer alloys, polyethylene terephthalate / polybutylene terephthalate, styrene-maleic anhydride / acrylonitrile-butadiene-styrene, polyether ether ketone / polyether sulfone, styrene-butadiene rubber, polyethylene / nylon, polyethylene / polyacetal, ethylene propylene rubber (EPR), and the like, or combinations comprising at least one of the foregoing blends.
[0175] Examples of polymeric thermosets that can be used in the polymer foam include polyurethane, epoxy, phenolic, polyester, polyamide, silicone, etc., or combinations comprising at least one of the foregoing thermosets. Mixtures of thermosets, and mixtures of thermoplastic and thermoset resins can be used.
[0176] multilayer material As explained above, the multilayer materials according to the embodiments of the present disclosure provide favorable properties in terms of compressibility, compressive resilience, and compliance. When used as a thermal insulator between cells in a battery module, the insulation sheet formed using the aerogel composition can provide resistance to compressive deformation to accommodate the expansion of the cells due to the degradation and expansion of the active materials during the charge / discharge cycle of the battery. During the initial assembly of the battery module, a relatively low load of 1 MPa or less is generally applied to the thermal insulator, such as the multilayer materials disclosed herein. During use, for example, when the cells in the battery module expand or swell during the charge / discharge cycle, a load of up to about 5 MPa can be applied to the multilayer materials disclosed herein.
[0177] In an exemplary aspect, the present disclosure provides a multi-layer material, wherein the multi-layer material exhibits a compressibility of less than about 25% at about 25 kPa. Optionally, upon release from compression, the multi-layer material may be sufficiently resilient to return to at least about 80%, 75%, 65%, 60%, or 50% of its original thickness. In some embodiments, the multi-layer material exhibits a compressibility of less than about 25% in a range of about 25 kPa to about 35 kPa, preferably less than about 50% at about 50 kPa. In some embodiments, the multi-layer material exhibits a compressibility in a range of about 25% to about 50% at about 50 kPa. In an exemplary embodiment, the multi-layer material exhibits a compressibility of less than about 80% at about 245 kPa, e.g., less than about 70% at about 235 kPa. In an exemplary embodiment, the multi-layer material exhibits a compressibility of less than about 70% at about 345 kPa. The thermal conductivity of the multi-layer material including the reinforced aerogel composition is preferably maintained at less than about 25 mW / m*K when the multi-layer material is compressed.
[0178] As described herein, the multilayer material may include multiple layers of materials, such as insulating layers, thermally conductive layers, heat capacity layers, encapsulant layers, abrasion resistant layers, fire / flame retardant layers, heat reflective layers, compressible layers, e.g., compressible pads, sacrificial layers, or combinations thereof. The layer combinations and configurations of the multilayer material may be selected to obtain a desired combination of properties, e.g., compressibility, resilience, thermal performance, fire response, and other properties. In some embodiments, the multilayer material includes at least one compressible pad disposed between at least two layers of the reinforced aerogel composition. For example, the compressible pad may be a foam or other compressible material, such as polyolefin, polyurethane, phenolic, melamine, cellulose acetate, or polystyrene. In certain embodiments, the multilayer material may also include at least one layer of a thermally conductive or heat capacity layer and at least one of the multiple layers of the reinforced aerogel composition. The thermally conductive or heat capacity material may absorb and / or disperse heat within the multilayer material. In some embodiments, the multilayer material may further include a heat reflective layer. For example, the heat reflective layer may include a metal foil or sheet.
[0179] In embodiments of a multi-layer material including several layers, the layers can be attached to other layers by adhesive mechanisms selected from the group consisting of, for example, aerosol adhesives, urethane-based adhesives, acrylate adhesives, hot melt adhesives, epoxies, rubber resin adhesives, polyurethane composite adhesives, and combinations thereof. In some embodiments, the layers can be attached by non-adhesive mechanisms, for example, by mechanisms selected from the group consisting of frame bonding, needling, stitching, sealing bags, rivets, buttons, clamps, wraps, braces, and combinations thereof. In some embodiments, multiple layers can be attached together using any combination of the aforementioned adhesive and non-adhesive mechanisms.
[0180] Multi-layered material end product Multilayer materials according to embodiments of the present disclosure can be formed into a variety of end products. In the simplest configuration, the multilayer material can be in the form of a sheet. The sheet can be formed continuously or semi-continuously, for example as a rolled product, or sheets of the desired size and shape can be cut or otherwise formed from a larger sheet. The sheet material can be used to form a thermal barrier between battery cells. In other configurations, the reinforced aerogel composition can be formed into a pouch, for example to enclose a pouch cell of a battery, or into a cylinder to enclose a cylindrical battery cell.
[0181] The multi-layer materials of the present disclosure can be formed into a variety of three-dimensional forms, including paneling, pipe preforms, half-shell preforms, elbows, joints, pouches, cylinders, and other shapes typically required for the application of insulation materials for industrial and commercial applications.
[0182] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the content clearly dictates otherwise. As used in this specification and the appended claims, the term "or" is generally utilized in its sense including "and / or" unless the context clearly dictates otherwise.
[0183] As used herein, "about" means "approximately" or "nearly" and refers to ±5% of a numerical value in relation to a stated numerical value or range. In some embodiments, the term "about" may include conventional rounding to the nearest significant digit of a numerical value. Additionally, the phrase "about 'x' to 'y'" includes "about 'x' to about 'y'".
[0184] As used herein, the terms "composition" and "composition" are used interchangeably.
[0185] As used herein, the terms "compressible pad" and "compressible layer" are used interchangeably.
[0186] Within the context of this disclosure, the terms "aerogel," "aerogel material," or "aerogel matrix" refer to a gel that includes an interconnected framework with a corresponding network of interconnected pores integrated within the framework, that confines a gas, such as air, as a dispersed interstitial medium, and that is characterized by the following physical and structural properties (as determined by nitrogen porosimetry testing) that are attributable to aerogels: (a) an average pore size ranging from about 2 nm to about 100 nm; (b) a porosity of at least 80% or greater; and (c) a porosity of at least about 100 nm. 2 / g or more surface area.
[0187] Thus, the aerogel materials of the present disclosure include any aerogel or other open-cell type material that satisfies the defining elements set forth in the preceding paragraph, including materials that can otherwise be classified as xerogels, cryogels, ambigels, microporous materials, etc.
[0188] Additionally, the aerogel material may be further characterized by additional physical properties including: (d) a pore volume of about 2.0 mL / g or more, particularly about 3.0 mL / g or more; (e) a density of about 0.50 g / cc or less, particularly about 0.3 g / cc or less, more particularly about 0.25 g / cc or less; and (f) at least 50% of the total pore volume comprises pores having a pore size between 2 and 50 nm (although, as described in more detail below, embodiments disclosed herein include aerogel scaffolds and compositions that include pores having a pore size greater than 50 nm). However, characterization of the compound as an aerogel material is not required to meet these additional properties.
[0189] Within the context of this disclosure, the term "aerogel composition" refers to any composite material that includes an aerogel material as a component of the composition. Examples of aerogel compositions include, but are not limited to, fiber-reinforced aerogel composites, aerogel composites that include added elements such as opacifiers, aerogel composites reinforced by an open-cell macroporous scaffold, aerogel-polymer composites, and composite materials in which aerogel particulates, particles, granules, beads, or powders are incorporated into a solid or semi-solid material in conjunction with binders, resins, cements, foams, polymers, or similar solid materials. Aerogel compositions are generally obtained from the various gel materials disclosed herein after removal of the solvent. Thus, the aerogel composition may further undergo additional processing or treatment. Also, the various gel materials may undergo other additional processing or treatment known or useful in the art before undergoing solvent removal (or liquid extraction or liquid drying).
[0190] The aerogel compositions of the present disclosure can include reinforced aerogel compositions. Within the context of the present disclosure, the term "reinforced aerogel composition" refers to an aerogel composition that includes a reinforcing phase within the aerogel material, where the reinforcing phase is not part of the aerogel framework itself.
[0191] Within the context of this disclosure, the term "fiber reinforced aerogel composition" refers to a reinforced aerogel composition that includes a fiber reinforcement as the reinforcing phase. Examples of fiber reinforcement include, but are not limited to, discrete fibers, woven materials, dry laid nonwoven materials, wet laid nonwoven materials, needle punched nonwovens, batting, webs, mats, felts, and / or combinations thereof.
[0192] The fiber reinforcement can be selected from organic polymer-based fibers, inorganic fibers, carbon-based fibers, or combinations thereof. The fiber reinforcement can include a variety of materials, including, but not limited to, polyester; polyolefin terephthalate; poly(ethylene) naphthalate; polycarbonate (e.g., rayon, nylon); cotton (e.g., Lycra from DuPont); carbon (e.g., graphite); polyacrylonitrile (PAN); oxidized PAN, uncarbonized heat-treated PAN (such as those from SGL carbon); glass or glass fiber-based materials (S-glass, 901 glass, 902 glass, 475 glass, E glass, etc.); silica-based fibers such as quartz (e.g., Quartz from Saint-Gobain); Q-felt (Johns Polyaramid fibers such as Manville, Saffil, Durablanket (Unifrax), and other silica fibers, Duraback (Carborundum), Kevlar, Nomex, Sontera (all from DuPont), and Conex (Taijin); polyolefins such as Tyvek (DuPont), Dyneema (DSM), and Spectra (Honeywell); other polypropylene fibers such as Typer and Xavan (both from DuPont); fluoropolymers such as PTFE, which has the trade names Teflon (DuPont) and Goretex (WLGORE); Nicalon (COI Examples of suitable fiber reinforcements include silicon carbide fibers such as silicon carbide fibers (Ceramics); ceramic fibers such as Nextel (3M); acrylic polymers; fibers such as wool, silk, linen, leather, suede; liquid crystal materials such as PBO-Zylon fibers (Tyobo), Vectan (Hoechst), Cambrelle fibers (DuPont); polyurethane, polyamide, wood fibers, boron, aluminum, iron, stainless steel fibers, and other thermoplastics such as PEEK, PES, PEI, PEK, PPS, etc. Glass or fiberglass-based fiber reinforcements may be manufactured using one or more techniques. In certain embodiments, it is desirable to make the materials using carding and cross-lapping or airlaid processes.In exemplary embodiments, carded and cross-wrapped glass or fiberglass based fiber reinforcements offer certain advantages over airlaid materials. For example, carded and cross-wrapped glass or fiberglass based fiber reinforcements can provide a consistent material thickness for a given basis weight of the reinforcement. In certain additional embodiments, it may be desirable to further needle the fiber reinforcement, requiring interweaving of the fibers in the z-direction, to enhance the mechanical and other properties of the final aerogel composition.
[0193] Within the context of this disclosure, reference to "thermal runaway" generally refers to a sudden, rapid increase in cell temperature and pressure due to various operating factors, and thermal runaway may even result in the propagation of excessive temperatures throughout the associated module. Potential causes of thermal runaway in such systems may include, for example, cell defects and / or shorts (both internal and external), cell insulation breakdown or rupture such as overcharging, accidental events, and the like, and excessive ambient temperatures (e.g., temperatures typically greater than 55°C). In normal use, cells heat up as a result of internal resistance. Under normal power / current loads and ambient operating conditions, the temperature within most Li-ion cells can be relatively easily controlled to remain in the range of 20°C to 55°C. However, under stressful conditions such as high power draw at high cell / ambient temperatures, as well as individual cell defects, localized heating may increase suddenly. In particular, above a critical temperature, exothermic chemical reactions within the cells become active. Furthermore, chemical heat generation generally results in a rapid increase in temperature. As a result, the heat generation is much greater than the available heat dissipation. Thermal runaway can cause the temperature at the cell's vent and inside to exceed 200°C.
[0194] Within the context of this disclosure, the term "foam" refers to a material that includes a skeleton of interconnected polymeric structures of substantially uniform composition with a corresponding network or collection of pores integrated within the skeleton, the foam being formed by dispersing a percentage of gas in the form of bubbles in a liquid or resin foam material, so that the bubbles are retained as pores when the foam material solidifies into a solid structure. In general, foams can be made using a variety of processes. See, for example, U.S. Patent Nos. 6,147,134, 5,889,071, 6,187,831, and 5,229,429. Thus, the foam material of the present disclosure includes any material that satisfies the defining elements described in this paragraph, including compounds that can otherwise be classified as OCMF materials, macroporous materials, etc. Foams as defined in this disclosure can be of the thermoplastic, elastomeric, and thermosetting (duromeric) types.
[0195] Within the context of the present disclosure, the terms "flexible" and "flexibility" refer to the ability of a material or composition to bend or flex without macrostructural failure. The insulating layer of the present disclosure is capable of bending at least 5°, at least 25°, at least 45°, at least 65°, or at least 85° without macroscopic failure, and / or has a bend radius of less than 4 feet, less than 2 feet, less than 1 foot, less than 6 inches, less than 3 inches, less than 2 inches, less than 1 inch, or less than U inches without macroscopic failure. Similarly, the terms "highly flexible" or "high flexibility" refer to a material capable of bending at least 90° without macroscopic failure, and / or has a bend radius of less than U inches. Additionally, the terms "classified flexibility" and "classified as flexible" refer to a material or composition that can be classified as flexible according to ASTM C1101 (ASTM International, West Conshohocken, PA).
[0196] The insulating layers of the present disclosure can be flexible, more highly flexible, and / or graded flexible. The aerogel compositions of the present disclosure can also be drapeable. Within the context of the present disclosure, the terms "drapeable" and "drape-ability" refer to the ability of a material to bend or flex 90° or more without macroscopic failure and with a radius of curvature of about 4 inches or less. The insulating layers according to certain embodiments of the present disclosure are flexible such that the compositions are non-rigid, and the compositions can be applied and conformed to a three-dimensional surface or object, or preformed into various shapes and configurations for ease of installation or application.
[0197] Within the context of this disclosure, the term "additive" or "additive element" refers to a material that can be added to an aerogel composition before, during, or after aerogel formation. Additives can be added to alter or improve desirable properties of the aerogel or to weaken undesirable properties of the aerogel. Generally, additives are added to the aerogel material either before gelling to a precursor liquid, during gelling to a transition state material, or after gelling to a solid or semi-solid material.
[0198] Examples of additives include, but are not limited to, microfibers, fillers, reinforcing agents, stabilizers, thickening agents, elastic compounds, opacifiers, coloring or pigment compounds, radiation absorbing compounds, radiation reflecting compounds, fire rating additives, corrosion inhibitors, heat conductive components, components providing thermal capacitance, phase change materials, pH modifiers, redox modifiers, HCN mitigation agents, off-gassing mitigation agents, conductive compounds, dielectric compounds, magnetic compounds, radar blocking components, hardening agents, shrinkage prevention agents, and other aerogel additives known to those skilled in the art. In some embodiments, the components providing thermal capacitance may include a material having a specific heat capacity of at least about 0.3 J / (g·°C). In some embodiments, the materials providing thermal capacitance have a specific heat capacity of at least about 0.5 J / (g·°C). For example, the materials providing thermal capacitance may include metals such as aluminum, titanium, nickel, steel, iron, or combinations thereof. In some embodiments, the multi-layer materials may include one or more layers or coatings of materials providing thermal capacitance. In some embodiments, the multi-layer material can include particles of a material that provides thermal capacitance disposed within one or more insulating layers that include an aerogel composition.
[0199] In certain embodiments, the aerogel compositions, reinforced aerogel compositions, and multilayer materials disclosed herein can be subjected to a high temperature event, e.g., can provide thermal protection during a high temperature event as disclosed herein. A high temperature event can be a temperature rise of at least about 1 cm for at least 2 seconds. 2 At least about 25 kW / m over an area of 2 , at least about 30 kW / m 2 , at least about 35 kW / m 2 , or at least about 40 kW / m 2 It is characterized by a sustained heat flux of about 40 kW / m 2Heat fluxes of at least about 10 cm for a duration of at least 1 minute are related to the heat fluxes resulting from a typical fire (Behavior of Charring Solids under Fire-Level Heat Fluxes; Milosavljevic, I., Suuberg, EM; NISTIR 5499; September 1994). In special cases, high temperature events can reach temperatures of at least about 10 cm for a duration of at least 1 minute. 2 This results in a heat flux of approximately 40 kW / m over an area of
[0200] Within the context of this disclosure, the terms "thermal conductivity" and "TC" refer to a measurement of the ability of a material or composition to transfer heat between two surfaces on either side of the material or composition where there is a temperature difference between the two surfaces. Thermal conductivity is specifically measured as the heat energy transferred per unit time and per unit surface area divided by the temperature difference. It is usually recorded in SI units as mW / m*K (milliwatts per meter*Kelvin). The thermal conductivity of a material may be determined by the following test methods known in the art: Test methods include, but are not limited to, Test Method for Steady-State Thermal Transmission Properties by Means of the Heat Flow Meter Apparatus (ASTM C518, ASTM International, West Conshohocken, PA), Test Method for Steady-State Heat Flux Measurements and Thermal Transmission Properties by Means of the Guarded-Hot-Plate Apparatus (ASTM C177, ASTM International, West Conshohocken,PA), Test Method for Steady-State Heat Transfer Properties of Pipe Insulation(ASTM C335,ASTM International,West Conshohocken,PA), Thin Heater Thermal Conductivity Test(ASTM C1114,ASTM International,West Conshohocken,PA), Standard Test Method for Thermal Transmission Properties of Thermally Conductive Electrical Insulation Materials(ASTM D5470,ASTM International,West Conshohocken,PA), Determination of thermal resistance by means of guarded hot plate and heat flow meter methods (EN 12667, British Standards Institution, United Kingdom), or Determination of steady-state thermal resistance and related properties-Guarded hot plate apparatus (ISO 8203, International Organization for Standardization, Switzerland). It is understood that, with different methods sometimes leading to different results, within the context of this disclosure, unless expressly stated otherwise, thermal conductivity measurements are taken in accordance with the ASTM C518 standard (Test Method for Steady-State Thermal Transmission Properties by Means of the Heat Flow Meter Apparatus) at a temperature of about 37.5°C at ambient atmospheric pressure and under a compressive load of about 2 psi. Measurements reported as per ASTM C518 generally correlate well with any of the measurements made as per EN 12667 with any relevant adjustment for compressive load.
[0201] Thermal conductivity measurements are also obtained at a temperature of about 10° C. at atmospheric pressure during compression. Thermal conductivity measurements at 10° C. are generally 0.5 to 0.7 mW / mK lower than corresponding thermal conductivity measurements at 37.5° C. In certain embodiments, the insulating layer of the present disclosure has a thermal conductivity at 10° C. of about 40 mW / mK or less, about 30 mW / mK or less, about 25 mW / mK or less, about 20 mW / mK or less, about 18 mW / mK or less, about 16 mW / mK or less, about 14 mW / mK or less, about 12 mW / mK or less, about 10 mW / mK or less, about 5 mW / mK or less, or a range between any two of these values.
[0202] Within the context of this disclosure, the term "density" refers to a measure of the mass per unit volume of a material or composition. The term "density" generally refers to the apparent density of a material, and similarly to the bulk density of a composition. Density is generally expressed in kg / m 3The density of a material or composition, such as the density of an aerogel, may be determined by methods known in the art, including, but not limited to, Standard Test Method for Dimensions and Density of Preformed Block and Board-Type Thermal Insulation (ASTM C303, ASTM International, West Conshohocken, PA), Standard Test Methods for Thickness and Density of Blanket or Batt Thermal Insulations (ASTM C167, ASTM International, West Conshohocken, PA), Determination of the apparent density of preformed pipe insulation (EN 13470, British Standards Institution, United Kingdom), or Determination of the apparent density of preformed pipe insulation (ISO 18098, International Organization for Standardization, Switzerland). It is to be understood that, with different methods sometimes yielding different results, within the context of this disclosure, density measurements are taken in accordance with ASTM C167 standard (Standard Test Methods for Thickness and Density of Blanket or Batt Thermal Insulations) for thickness measurements at a compression force of 2 psi unless otherwise noted.In certain embodiments, the aerogel material or composition of the present disclosure has a density of about 1.0 g / cc or less, about 0.90 g / cc or less, about 0.80 g / cc or less, about 0.70 g / cc or less, about 0.60 g / cc or less, about 0.50 g / cc or less, about 0.40 g / cc or less, about 0.30 g / cc or less, about 0.25 g / cc or less, about 0.20 g / cc or less, about 0.18 g / cc or less, about 0.16 g / cc or less, about 0.14 g / cc or less, about 0.12 g / cc or less, about 0.10 g / cc or less, about 0.05 g / cc or less, about 0.01 g / cc or less, or a range between any two of these values.
[0203] The hydrophobicity of an aerogel material or composition can be expressed in terms of water vapor uptake. Within the context of this disclosure, the term "water vapor uptake" refers to a measurement of the potential of an aerogel material or composition to absorb water vapor. Water vapor uptake can be expressed as the percentage (by weight) of water that an aerogel material or composition absorbs or otherwise retains when exposed to water vapor at specific measurement conditions. The water vapor uptake of an aerogel material or composition can be determined by methods known in the art. Known methods include, but are not limited to, Standard Test Method for Determining the Water Vapor Sorption of Unfaced Mineral Fiber Insulation (ASTM C1104, ASTM International, West Conshohocken, PA), Thermal insulating products for building applications, Determination of long term water absorption by diffusion (EN 12088, British Standards Institution, United Kingdom). It should be understood that, with different methods sometimes yielding different results, within the context of this disclosure, water vapor uptake measurements are taken at 49°C and 95% humidity under ambient pressure for 24 hours (modified from 96 hours per ASTM C1104) in accordance with ASTM C1104 (Standard Test Method for Determining the Water Vapor Sorption of Unfaced Mineral Fiber Insulation) unless otherwise noted. In certain embodiments, the aerogel materials or compositions of the present disclosure may have a water vapor uptake of about 50 wt% or less, about 40 wt% or less, about 30 wt% or less, about 20 wt% or less, about 15 wt% or less, about 10 wt% or less, about 8 wt% or less, about 3 wt% or less, about 2 wt% or less, about 1 wt% or less, about 0.1 wt% or less, or a range between any two of these values.An aerogel material or composition that has improved water vapor uptake relative to another aerogel material or composition will have a lower rate of water vapor uptake / retention relative to the baseline aerogel material or composition.
[0204] The hydrophobicity of an aerogel material or composition can be expressed by measuring the equilibrium contact angle of a water droplet at the interface with the surface of the material. The aerogel materials or compositions of the present disclosure can have a water contact angle of about 90° or more, about 120° or more, about 130° or more, about 140° or more, about 150° or more, about 160° or more, about 170° or more, about 175° or more, or in a range between any two of these values.
[0205] Within the context of this disclosure, the terms "heat of combustion," "HOC," and "ΔHC" refer to a measurement of the amount of heat energy released upon combustion or exothermic decomposition of a material or composition. Heat of combustion is generally recorded in units of calories of heat energy released per gram of aerogel material or composition (cal / g) or in units of megajoules of heat energy released per kilogram of material or composition (MJ / kg). The heat of combustion of a material or composition may be determined by methods known in the art, including, but not limited to, Reaction to fire tests for products-Determination of the gross heat of combustion (calorific value) (EN ISO 1716, International Organization for Standardization, Switzerland; EN adopted). Within the context of this disclosure, measurements of heat of combustion are obtained in accordance with the EN ISO 1716 standard (Reaction to fire tests for products-Determination of the gross heat of combustion (calorific value)) unless otherwise noted.
[0206] Within the context of this disclosure, all thermal analyses and related definitions refer to measurements made in air at ambient pressure, starting at 25° C. and increasing at a rate of 20° C. per minute up to a maximum of 1000° C. Therefore, any changes in these parameters must be taken into account (or must be re-performed under these conditions) when measuring and calculating the onset temperature of pyrolysis, peak temperature of heat release, peak temperature of heat absorption, etc.
[0207] Within the context of this disclosure, the terms "onset temperature of thermal decomposition" and "TD" refer to the measurement of the lowest temperature of the ambient heat at which a rapid exothermic reaction from the decomposition of an organic material appears in a material or composition. Thermogravimetric analysis (TGA) can be used to measure the onset temperature of thermal decomposition of an organic material in a material or composition. The TGA curve of a material shows the weight loss (% mass) of the material when it is exposed to an increase in ambient temperature, thus indicating thermal decomposition. The onset temperature of thermal decomposition of a material can be correlated to the intersection of the tangents of the following TGA curves: a straight line tangent to the baseline of the TGA curve, and a straight line tangent to the TGA curve at the maximum slope during the rapid exothermic decomposition event for the decomposition of the organic material. Within the context of this disclosure, the measurement of the onset temperature of thermal decomposition of an organic material is obtained using TGA analysis as provided in this paragraph, unless otherwise specified.
[0208] Differential scanning calorimetry (DSC) analysis may also be used to measure the onset temperature of thermal decomposition of a material. The DSC curve of a material indicates the heat energy (mW / mg) released by the material when it is exposed to a gradual increase in ambient temperature. The onset temperature of thermal decomposition of a material can be correlated with the point on the DSC curve where ΔmW / mg (change in heat energy output) increases by a maximum, and thus the DSC curve indicates the amount of heat generated from the aerogel material. Within the context of this disclosure, measurements of the onset temperature of thermal decomposition using DSC, TGA, or both are obtained using a temperature ramp rate of 20° C. / min, as further defined in the preceding paragraph, unless expressly stated otherwise. DSC and TGA each provide a similar value for this onset temperature of thermal decomposition, and many times, tests are run simultaneously, with test results obtained from both DSC and TGA.
[0209] Within the context of this disclosure, the terms "endothermic decomposition onset temperature" and "TED" refer to the measurement of the lowest temperature of the ambient heat at which an endothermic reaction from decomposition or dehydration appears in a material or composition. Thermogravimetric analysis (TGA) can be used to measure the onset temperature of endothermic decomposition in a material or composition. The TGA curve of a material shows the weight loss (% mass) of the material as it is exposed to an increase in ambient temperature. The onset temperature of thermal decomposition of a material can be correlated to the intersection of the tangents of the following TGA curves: a line tangent to the baseline of the TGA curve, and a line tangent to the TGA curve at the maximum slope point during the period of rapid endothermic decomposition or dehydration of the material. Within the context of this disclosure, the measurement of the onset temperature of endothermic decomposition of a material or composition is obtained using TGA analysis as provided in this paragraph, unless otherwise specified.
[0210] Within the context of this disclosure, the terms "furnace temperature rise" and "ΔTR" refer to a measurement of the difference between the maximum temperature (TMAX) of a material or composition under pyrolysis conditions compared to a reference temperature of that material or composition under pyrolysis conditions (usually the final temperature or TFIN). The furnace temperature rise is generally recorded in degrees Celsius or °C. The furnace temperature rise of a material or composition can be determined by methods known in the art, including, but not limited to, Reaction to fire tests for building and transport products: Non-combustibility test (EN ISO 1182, International Organization for Standardization, Switzerland; EN adopted). Within the context of this disclosure, furnace temperature rise measurements are obtained according to conditions equivalent to the EN ISO 1182 standard (Reaction to fire tests for building and transport products: Non-combustibility test) unless otherwise specified. In certain embodiments, the aerogel compositions of the present disclosure may provide an oven temperature rise of about 100° C. or less, about 90° C. or less, about 80° C. or less, about 70° C. or less, about 60° C. or less, about 50° C. or less, about 45° C. or less, about 40° C. or less, about 38° C. or less, about 36° C. or less, about 34° C. or less, about 32° C. or less, about 30° C. or less, about 28° C. or less, about 26° C. or less, about 24° C. or less, or a range between any two of these values. Within the context of the stability of the composition at elevated temperatures, for example, an improvement of the first composition over the second composition would be contemplated for a first composition having a lower oven temperature rise than the oven temperature rise of the second composition. It is contemplated herein that the oven temperature rise of the composition is reduced when one or more fire-rated additives are added as compared to the composition.
[0211] Within the context of this disclosure, the terms "flame time" and "TFLAME" refer to a measurement of the duration of a flame of a material or composition under pyrolytic conditions, where "flame time duration" is the duration of a flame in any part of the visible portion of a test sample that lasts for 5 seconds or more. Flame times are typically recorded in seconds or minutes. The flame time of a material or composition may be determined by methods known in the art, including, but not limited to, Reaction to fire tests for building and transport products: Non-combustibility test (EN ISO 1182, International Organization for Standardization, Switzerland; EN adopted). Within the context of this disclosure, flame time measurements are obtained according to conditions equivalent to the EN ISO 1182 standard (Reaction to fire tests for building and transport products: Non-combustibility test), unless otherwise specified. In certain embodiments, the aerogel compositions of the present disclosure have a flame time of about 30 seconds or less, about 25 seconds or less, about 20 seconds or less, about 15 seconds or less, about 10 seconds or less, about 5 seconds or less, about 2 seconds or less, or a range between any two of these values. Within the context of this specification, for example, an improvement of the first composition over the second composition would be considered for a first composition having a flame time that is less than the flame time of a second composition. It is contemplated herein that the flame time of a composition is reduced when one or more fire-rated additives are added compared to a composition that does not include any fire-rated additives.
[0212] Within the context of this disclosure, the terms "mass loss" and "ΔM" refer to a measurement of the amount of a material, composition, or composition that is lost or incinerated under pyrolytic conditions. Mass loss is typically reported in weight percent or wt%. The mass loss of a material, composition, or composition can be determined by methods known in the art, including but not limited to Reaction to fire tests for building and transport products: Noncombustibility test (EN ISO 1182, International Organization for Standardization, Switzerland; EN adopted). Within the context of this disclosure, mass loss measurements are obtained according to conditions equivalent to the EN ISO 1182 standard (Reaction to fire tests for building and transport products: Non-combustibility test), unless otherwise specified. In certain embodiments, the insulating layer or aerogel composition of the present disclosure may have a mass loss of about 50% or less, about 40% or less, about 30% or less, about 28% or less, about 26% or less, about 24% or less, about 22% or less, about 20% or less, about 18% or less, about 16% or less, or a range between any two of these values. Within the context of this specification, for example, an improvement of the first composition over the second composition would be considered for a first composition having a mass loss that is less than the mass loss of a second composition. It is contemplated herein that the mass loss of a composition is reduced when one or more fire-rated additives are added compared to a composition that does not include any fire-rated additives.
[0213] Within the context of this disclosure, the term "peak heat release temperature" refers to a measurement of the temperature of the ambient heat at which the exothermic heat release from decomposition is maximum. TGA analysis, differential scanning calorimetry (DSC), or a combination thereof may be used to measure the peak heat release temperature of a material or composition. DSC and TGA will each provide similar values of peak heat release temperature. And many times, tests are run simultaneously so that results are obtained from both DSC and TGA. In a typical DSC analysis, heat flow is plotted against increasing temperature, and the peak heat release temperature is the temperature at which the highest peak of such curve occurs. Within the context of this disclosure, measurements of the peak heat release temperature of a material or composition are obtained using TGA analysis as provided in this paragraph, unless otherwise noted.
[0214] In the context of endothermic materials, the term "peak heat absorption temperature" refers to a measurement of the temperature of the environmental heat at which the heat absorption of the endotherm from decomposition is maximum. TGA analysis, differential scanning calorimetry (DSC), or a combination thereof may be used to measure the peak heat absorption temperature of a material or composition. In a typical DSC analysis, heat flow is plotted against increasing temperature, and the peak heat absorption temperature is the temperature at which the lowest peak of such a curve occurs. Within the context of this disclosure, the measurement of the peak heat absorption temperature of a material or composition is obtained using TGA analysis as provided in this paragraph, unless otherwise specified.
[0215] Within the context of this disclosure, the terms "low flammability" and "lowly flammable" hereinafter refer to a material or composition that meets the combination of the following properties: i) furnace temperature rise of 50° C. or less, ii) flame time of 20 seconds or less, and iii) mass loss of 50 wt. % or less. Within the context of this disclosure, the terms "non-flammable" and "non-flammable" hereinafter refer to a material or composition that meets the combination of the following properties: i) furnace temperature rise of 40° C. or less, ii) flame time of 2 seconds or less, and iii) mass loss of 30 wt. % or less. As described herein, it is contemplated that the flammability of a composition (e.g., a combination of furnace temperature rise, flame time, and mass loss) is reduced upon inclusion of one or more fire-rated additives.
[0216] Within the context of this disclosure, the terms "low flammability" and "lowly flammable" refer to a low flammability material or composition having a total heat of combustion (HOC) of 3 MJ / kg or less. Within the context of this disclosure, the terms "non-flammability" and "non-combustible" refer to a non-flammable material or composition having a heat of combustion (HOC) of 2 MJ / kg or less. It is contemplated that the HOC of a composition is reduced upon inclusion of one or more fire-rated additives, as described herein.
[0217] Within the context of this disclosure, the term "hydrophobically bonded silicon" refers to silicon atoms in the backbone of a gel or aerogel that contain at least one hydrophobic group covalently bonded to the silicon atom. Examples of hydrophobically bonded silicon include, but are not limited to, silicon atoms of silica groups in a gel backbone formed from a gel precursor that contains at least one hydrophobic group (such as MTES or DMDS). Hydrophobically bonded silicon may also include, but is not limited to, silicon atoms on the gel backbone or surface of the gel that are treated with a hydrophobizing agent (such as HMDZ) to impart or improve hydrophobicity by incorporating additional hydrophobic groups into the composition. Hydrophobic groups of the present disclosure include, but are not limited to, methyl, ethyl, propyl, isopropyl, butyl, isopropyl, tert-butyl, octyl, phenyl, or other substituted or unsubstituted hydrophobic organic groups known to those skilled in the art. Within the context of this disclosure, the terms "hydrophobic groups", "hydrophobic organic material" and "hydrophobic organic content" specifically exclude easily hydrolyzable organosilicon-bonded alkoxy groups on the backbone of the gel material that are the reaction product of organic solvents with silanol groups. Such excluded groups are distinguishable from this hydrophobic organic content by NMR analysis. NMR spectroscopy such as CP / MAS29Si Solid State NMR can be used to analyze the amount of hydrophobically bonded silicon encapsulated in the aerogel. NMR analysis of the aerogel allows the characterization and associated quantification of M-type hydrophobically bonded silicon (monofunctional silica such as TMS derivatives), D-type hydrophobically bonded silicon (bifunctional silica such as DMDS derivatives), T-type hydrophobically bonded silicon (trifunctional silica such as MTES derivatives) and Q-type silicon (tetrafunctional silica such as TEOS derivatives). NMR analysis can also be used to analyze the bonding chemistry of hydrophobic silicon contained in aerogels by allowing categorization of specific types of hydrophobically bonded silicon into subtypes (such as categorizing T-type hydrophobic silicon into T1, T2, and T3 species).Specific details regarding NMR analysis of silica materials can be found in the paper by Geppi et al., "Applications of Solid-State NMR to the Study of Organic / Inorganic Multicomponent Materials," Appl. Spec. Rev. (2008), 44-1:1-89, specifically pages 7-9, which is hereby incorporated by reference according to the specifically cited pages.
[0218] Characterization of hydrophobically bonded silicon in CP / MAS29SiNMR can be analyzed based on the following chemical shift peaks: M1 (30-10 ppm); D1 (10-10 ppm), D2 (-10-20 ppm); T1 (-30-40 ppm), T2 (-40-50 ppm), T3 (-50-70 ppm); Q2 (-70-85 ppm), Q3 (-85-95 ppm), Q4 (-95-110 ppm). These chemical shift peaks are approximate and illustrative, and are not intended to be limiting or restrictive. The exact chemical shift peaks due to various silicon species in a material may depend on the specific chemical composition of the material, and generally can be deciphered by those skilled in the art through routine experimentation and analysis.
[0219] Within the context of this disclosure, the term "hydrophobic organic content" or "hydrophobe content" or "hydrophobic content" refers to the amount of hydrophobic organic material bound to the backbone of an aerogel material or composition. The hydrophobic organic content of an aerogel material or composition can be expressed as a weight percentage of the amount of hydrophobic organic material on the aerogel backbone compared to the total amount of material of the aerogel material or composition. The hydrophobic organic content can be calculated by one of ordinary skill in the art based on the nature and relative concentrations of the materials used in producing the aerogel material or composition. Thermogravimetric analysis (TGA) of the subject material can also be used to measure the hydrophobic organic content, preferably in an oxygen atmosphere (although TGA in alternative gas environments is also useful). Specifically, the percentage of hydrophobic organic material in an aerogel can be correlated to the percentage of weight loss of the hydrophobic aerogel material or composition when exposed to combustion heat temperatures during TGA analysis, with adjustments being made for loss of moisture, loss of residual solvent, and loss of easily hydrolyzable alkoxy groups during TGA analysis. Other alternative techniques such as differential scanning calorimetry, elemental analysis (especially carbon), chromatographic techniques, nuclear magnetic resonance spectroscopy, and other analytical techniques known to those skilled in the art may be used to measure and determine the hydrophobic content of the aerogel compositions of the present disclosure. In some cases, a combination of known techniques may be useful or necessary in determining the hydrophobic content of the aerogel compositions of the present disclosure.
[0220] The aerogel materials or compositions of the present disclosure can have a hydrophobic organic content of 50 wt% or less, 40 wt% or less, 30 wt% or less, 25 wt% or less, 20 wt% or less, 15 wt% or less, 10 wt% or less, 8 wt% or less, 6 wt% or less, 5 wt% or less, 4 wt% or less, 3 wt% or less, 2 wt% or less, 1 wt% or less, or a range between any two of these values.
[0221] The term "fuel content" refers to the total amount of combustibles in an aerogel material or composition, which may be correlated to the total percentage weight loss of an aerogel material or composition when exposed to heat of combustion temperatures during TGA or TG-DSC analysis, with an adjustment made for water loss. The fuel content of an aerogel material or composition may include hydrophobic organic content, as well as other flammable residual alcohol solvents, fillers, reinforcing materials, and easily hydrolyzable alkoxy groups.
[0222] Within the context of this disclosure, the term "ormosil" includes the aforementioned materials, as well as other organically modified materials, sometimes also referred to as "ormocera". Ormosils are often used as coatings where an ormosil film is coated onto a substrate, for example, through a sol-gel process. Examples of other organic-inorganic hybrid aerogels of the present disclosure include, but are not limited to, silica-polyether, silica-PMMA, silica-chitosan, carbides, nitrides, and other combinations of the aforementioned organic-inorganic aerogels forming compounds. Published U.S. Patent Application No. 20050192367 (paragraphs
[0022] -
[0038] and
[0044] -
[0058] ) contains teachings of such hybrid organic-inorganic materials and is hereby incorporated by reference according to the individually cited sections and paragraphs.
[0223] Use of multi-layer materials within a battery module or battery pack Lithium-ion batteries (LIBs) are considered to be one of the most important energy storage technologies due to their high operating voltage, low memory effect, and high energy density compared to conventional batteries. However, safety concerns are a significant barrier preventing the large-scale use of LIBs. Under extreme conditions, exothermic reactions can result in heat release that can trigger subsequent dangerous reactions. The situation worsens when heat release from cells under extreme conditions can activate chain reactions, resulting in sudden thermal runaway.
[0224] With the continuous improvement of the energy density of LIBs, it becomes increasingly urgent to enhance their safety for the development of electric devices, e.g., electric vehicles. The mechanisms behind the safety issues vary for different battery chemistries. The present technology focuses on preparing multi-layer materials and corresponding configurations of the prepared materials to obtain favorable thermal and mechanical properties. The present technology's multi-layer materials ensure the stability of LIBs under normal operation modes (e.g., withstanding applied compressive stress) while providing effective heat dissipation measures under normal conditions as well as under thermal runaway conditions.
[0225] The multilayer materials disclosed herein are useful for isolating, insulating, and protecting battery cells or battery components of any configuration of battery, such as pouch cells, cylindrical cells, prismatic cells, as well as packs and modules incorporating or including any such cells. The multilayer materials disclosed herein are useful in rechargeable batteries, such as lithium ion batteries, solid state batteries, and any other energy storage device or technology requiring isolation, insulation, and protection.
[0226] Passive devices such as cooling systems may be used in conjunction with the multi-layer materials of the present disclosure within a battery module or battery pack.
[0227] The multi-layer materials according to various embodiments of the present disclosure of battery packs include multiple single battery cells or modules of battery cells to thermally isolate the single battery cells or modules of battery cells from one another. Some of the embodiments of the invention related to the present invention are given below. [Embodiment 1] 1. A multi-layer material for use as a thermal barrier in an electrical energy storage system, said multi-layer material comprising: a core including an insulating layer, the insulating layer having a thermal conductivity through a thickness dimension of the insulating layer of less than about 50 mW / m·K at 25° C. and less than about 60 mW / m·K at 600° C.; an exterior disposed outside the core, the exterior including a thermally conductive layer, the thermally conductive layer having a thermal conductivity of at least about 200 mW / m·K along an in-plane dimension of the thermally conductive layer; The multi-layer material comprising: [Embodiment 2] 2. The multi-layer material of embodiment 1, wherein the thermally conductive layer is in contact with the insulating layer. [Embodiment 3] 3. The multilayer material of claim 1 or claim 2, wherein the thermally conductive layer is substantially L-shaped, a vertical portion of the L-shaped thermally conductive layer being spaced apart from the insulating layer, and a horizontal portion of the L-shaped thermally conductive layer being in contact with the insulating layer. [Embodiment 4] 2. The multilayer material of any one of the preceding embodiments, wherein the thermally conductive layer is divided into a first conductive layer and a second conductive layer on either side of the insulating layer, the first conductive layer and the second conductive layer being in contact with the insulating layer. [Embodiment 5] 2. The multilayer material of any one of the preceding embodiments, wherein the thermally conductive layer comprises at least one layer comprising a metal, carbon, a conductive polymer, or a combination thereof. [Embodiment 6] 5. The multilayer material of any one of the preceding claims, wherein the thermally conductive layer comprises a metal, including aluminum, copper, or steel. [Embodiment 7] 13. The multi-layer material of any one of the preceding embodiments, wherein the thermally conductive layer is an outer layer of the multi-layer material. [Embodiment 8] 11. The multi-layer material of any one of the preceding embodiments, wherein the thermally conductive layer is in a form selected from the group consisting of a mesh, a sheet, a perforated sheet, a foil, and a perforated foil. [Embodiment 9] 4. The multi-layer material of any of the preceding embodiments, wherein the insulating layer comprises mica, ceramic, inorganic fiber cotton, resin, or inorganic foam. [Embodiment 10] 13. The multilayer material of any one of the preceding embodiments, wherein the insulating layer comprises an aerogel. [Embodiment 11] 11. The multilayer material of embodiment 10, wherein the aerogel comprises a reinforcing material. [Embodiment 12] 12. The multi-layer material of embodiment 11, wherein the reinforcing material comprises fibers selected from organic polymer-based fibers, inorganic fibers, carbon-based fibers, or combinations thereof. [Embodiment 13] 13. The multi-layer material of embodiment 12, wherein the fibers are in the form of separate fibers, a woven material, a dry-laid nonwoven material, a wet-laid nonwoven material, a needle-punched nonwoven, a batting, a web, a mat, a felt, and / or combinations thereof. [Embodiment 14] 14. The multi-layer material of embodiment 12 or embodiment 13, wherein the inorganic fibers are selected from glass fibers, rock fibers, metal fibers, boron fibers, ceramic fibers, basalt fibers, or combinations thereof. [Embodiment 15] 15. The multilayer material of any one of embodiments 10 to 14, wherein the aerogel comprises a silica-based aerogel. [Embodiment 16] 16. The multilayer material of any one of claims 10-15, wherein the aerogel comprises one or more additives, and the one or more additives are present at a level of at least about 5-20 weight percent of the aerogel. [Embodiment 17] 17. The multilayer material of embodiment 16, wherein the one or more additives are present at a level of at least about 10-20 weight percent of the aerogel. [Embodiment 18] 18. The multi-layer material of embodiment 16 or embodiment 17, wherein the one or more additives comprises a fire-rated additive. [Embodiment 19] 18. The multilayer material of embodiment 16 or embodiment 17, wherein the one or more additives comprise an opacifying agent selected from BC, diatomaceous earth, manganese ferrite, MnO, NiO, SnO, AgO, BiO, TiC, WC, carbon black, titanium dioxide, iron titanium oxide, zirconium silicate, zirconium oxide, iron (I) oxide, iron (III) oxide, manganese dioxide, iron titanium oxide (ilmenite), chromium oxide, or mixtures thereof. [Embodiment 20] 17. The multilayer material of embodiment 16, wherein the one or more additives comprises an opacifying agent comprising silicon carbide. [Embodiment 21] 17. The multi-layer material of embodiment 16, wherein the one or more additives comprise a combination of a fire-rated additive and an opacifier. [Embodiment 22] 22. The multilayer material of any one of embodiments 10-21, wherein the aerogel has a density in the range of about 0.25 g / cc to about 1.0 g / cc. [Embodiment 23] 23. The multilayer material of any one of embodiments 10 to 22, wherein the aerogel has a flexural modulus of about 2 MPa to about 8 MPa. [Embodiment 24] 24. The multilayer material of any one of embodiments 10-23, wherein the aerogel exhibits compression resistance, the compression resistance at 25% strain being between about 40 kPa and about 180 kPa. [Embodiment 25] 2. The multilayer material of any one of the preceding embodiments, further comprising a heat capacity layer disposed between a portion of the thermally conductive layer and the insulating layer, the heat capacity layer having a specific heat capacity of at least about 0.2 J / (g C). [Embodiment 26] 26. The multi-layer material of embodiment 25, wherein the heat capacity layer comprises a phase change material. [Embodiment 27] 26. The multilayer material of embodiment 25, wherein the heat capacity layer comprises a metal comprising aluminum, titanium, nickel, steel, or iron. [Embodiment 28] 2. The multilayer material of any one of the preceding embodiments, further comprising a sacrificial material layer disposed between a portion of the thermally conductive layer and the insulating layer. [Embodiment 29] 29. The multilayer material of embodiment 28, wherein the sacrificial material layer comprises a material selected from the group consisting of siloxane, polyolefin, polyurethane, phenolic, melamine, cellulose acetate, and polystyrene. [Embodiment 30] 30. The multilayer material of embodiment 28 or embodiment 29, wherein the sacrificial material layer is in the form of a foam. [Embodiment 31] 31. The multilayer material according to any one of embodiments 28 to 30, wherein the sacrificial material layer has an onset temperature of chemical decomposition in the range of about 200°C to about 400°C. [Embodiment 32] 2. The multilayer material of any one of the preceding embodiments, further comprising an encapsulation layer disposed between the thermally conductive layer and the insulating layer. [Embodiment 33] 33. The multilayer material of embodiment 32, wherein the encapsulating material layer comprises one or more polymer layers. [Embodiment 34] 4. The multilayer material of any one of the preceding embodiments, wherein the multilayer material has an average thickness in an uncompressed state of between about 2 mm and about 10 mm. [Embodiment 35] 2. The multilayer material of any one of the preceding embodiments, wherein the thermally conductive layer is substantially L-shaped, a vertical portion of the L-shaped thermally conductive layer is spaced apart from the insulating layer, a horizontal portion of the L-shaped thermally conductive layer is in contact with the insulating layer, and one or more of an encapsulating material layer, a sacrificial material layer, and a heat capacity layer are disposed between the vertical portion of the L-shaped thermally conductive layer and the insulating layer. [Embodiment 36] 13. The multi-layer material of any preceding embodiment, wherein the multi-layer material has a thermal resistivity of at least about 0.02 K / W. [Embodiment 37] 2. Use of the multilayer material according to any one of the preceding embodiments in a battery pack comprising a plurality of individual battery cells or a plurality of battery cell modules, for thermally isolating the individual battery cells or the battery cell modules from each other. [Embodiment 38] The use of embodiment 37, wherein a runaway event occurring in one or more battery cells or battery cell modules of a portion of the battery does not damage a battery cell or battery module of the portion of the battery that is separated from the portion of the battery where the runaway event occurs by the multilayer material of any one of embodiments 1 to 36. [Embodiment 39] a first battery cell having a first surface; a second battery cell having a second surface, the second surface facing the first surface; and A multilayer material according to any one of the preceding claims disposed between the first surface and the second surface; a heat exchange system in contact with the first battery cell, the second battery cell, and the thermally conductive layer of the multi-layer material; a battery module including: [Embodiment 40] 40. The battery module of embodiment 39, wherein the multilayer material of any one of embodiments 1-34 covers at least about 80% of the surface area of the opposing first and second surfaces. [Embodiment 41] A battery module as described in embodiment 39 or embodiment 40, wherein the insulating layer of the multilayer material extends into the heat exchange system. [Embodiment 42] 42. The battery module of any one of embodiments 39-41, wherein the thermally conductive layer of the multilayer material is in thermal communication with the heat exchange system. [Embodiment 43] 43. The battery module of any one of embodiments 39-42, wherein the thermally conductive layer of the multilayer material is in thermal communication with the first battery cell and / or the second battery cell. [Embodiment 44] 44. The battery module of embodiment 43, wherein the thermally conductive layer of the multilayer material is in contact with the first battery cell and / or the second battery cell. [Embodiment 45] 45. The battery module of any one of embodiments 39 to 44, wherein the battery module has a thermal resistance coefficient of at least 0.01, the thermal resistance coefficient being the ratio of the thermal resistance of the multilayer material to the areal energy density of the battery cells in the battery module, and the areal energy density of the array being the ratio of the total energy density of all cells in the array to the external surface of the array. [Embodiment 46] 46. The battery module of any one of embodiments 39 to 45, wherein the multilayer material has a thickness factor of at least about 0.3, the thickness factor being the ratio of the thickness of the multilayer material to the areal energy density of the battery cell. [Embodiment 47] A battery pack comprising a plurality of modules and one or more spacers disposed between adjacent modules, the one or more spacers comprising the multilayer material of any one of embodiments 1-36. [Embodiment 48] The battery pack according to embodiment 47, wherein at least one of the plurality of modules is the battery module according to any one of embodiments 39 to 46. [Embodiment 49] A battery pack as described in embodiment 47 or embodiment 48, wherein the insulating barrier of the multilayer material extends into the cooling system. [Embodiment 50] 50. The battery pack of any one of embodiments 47-49, wherein the thermally conductive layer of the multi-layer material is in thermal communication with the cooling system. [Embodiment 51] A device or vehicle comprising the battery pack according to any one of embodiments 47 to 50. [Embodiment 52] The device of embodiment 51, wherein the device is a laptop computer, a PDA, a mobile phone, a tag scanner, an audio device, a video device, a display panel, a video camera, a digital camera, a desktop computer, a military portable computer, a military telephone, a laser range finder, a digital communication device, a secret intelligence gathering sensor, an electronic integrated garment, a night vision device, a power tool, a calculator, a radio, a remote control device, a GPS device, a handheld and portable television, a car starter, a flashlight, an acoustic device, a portable heating device, a portable vacuum cleaner, or a portable medical tool. [Embodiment 53] 52. The vehicle of embodiment 51, wherein the vehicle is an electric vehicle. [Embodiment 54] 1. A method for designing an energy storage system, comprising: assembling one or more battery cell(s) to form an array; calculating an areal energy density of the array, the areal energy density of the array being a ratio of a total energy density of all cells in the array to an exterior surface of the array; selecting a thermal resistance and a thickness when compressed of a multi-layer material in accordance with the areal energy density of the array such that the energy storage system has a thermal resistance coefficient of at least about 0.01 and a thickness coefficient of at least about 0.3, the thickness coefficient being the ratio of the thickness of the multi-layer material to the areal energy density of the array and the thermal resistance coefficient being the ratio of the thermal resistance of the multi-layer material to the areal energy density of the array; disposing the multi-layer material within and / or around the array; The method comprising: [Embodiment 55] Selecting the thermal resistance and the compressed thickness calculating a thermal resistance coefficient of said multi-layer material; reading a minimum compressed thickness of said multi-layer material from a heat propagation map; selecting a compressed thickness greater than said minimum compressed thickness; 55. The method of embodiment 54, comprising: [Embodiment 56] Selecting the thermal resistance and the compressed thickness calculating a thickness factor for each battery cell of the array; Reading a minimum thermal resistance of the multi-layer material from a heat propagation map; selecting a thermal resistance of the multi-layer material greater than the minimum thermal resistance; 56. The method of embodiment 54 or embodiment 55, comprising: [Embodiment 57] disposing the multi-layer material; forming the multi-layer material separately from the array; inserting the multi-layer material adjacent to a battery cell of the array; 57. The method of any one of embodiments 54 to 56, comprising: [Embodiment 58] 58. The method of any one of embodiments 54 to 57, wherein disposing the multi-layered material comprises forming the multi-layered material in situ directly within and / or around the array. [Embodiment 59] 59. The method of embodiment 58, wherein disposing the multi-layer material comprises spraying, coating, depositing, or filling the multi-layer material into and / or around the array.
Claims
1. 1. A multi-layer material for use as a thermal barrier in an electrical energy storage system, said multi-layer material comprising: a core including an insulating layer, the insulating layer having a thermal conductivity through a thickness dimension of the insulating layer of less than about 50 mW / m K when measured according to ASTM C518 standard at 25° C., atmospheric pressure, and under a compressive load of 2 psi, and less than about 60 mW / m K when measured according to ASTM C518 standard at 600° C., atmospheric pressure, and under a compressive load of 2 psi; an exterior disposed outside the core, the exterior including a thermally conductive layer, the thermally conductive layer having a thermal conductivity along an in-plane dimension of the thermally conductive layer of at least about 200 mW / m K when measured according to ASTM C518 standard at 37.5° C., atmospheric pressure, and under a compressive load of 2 psi; Including, 11. The multi-layer material, wherein the thermally conductive layer is substantially L-shaped, a vertical portion of the L-shaped thermally conductive layer being spaced apart from the insulating layer, and a horizontal portion of the L-shaped thermally conductive layer being in contact with the insulating layer.
2. The multi-layer material of claim 1 , wherein the thermally conductive layer is in contact with the insulating layer.
3. 2. The multilayer material of claim 1, wherein the thermally conductive layer is divided into a first conductive layer and a second conductive layer on either side of the insulating layer, the first conductive layer and the second conductive layer being in contact with the insulating layer.
4. 10. The multi-layer material of claim 1, wherein the thermally conductive layer comprises at least one layer comprising a metal, carbon, a conductive polymer, or a combination thereof.
5. The multi-layer material of claim 1 , wherein the thermally conductive layer comprises a metal including aluminum, copper, or steel.
6. The multi-layer material of claim 1 , wherein the thermally conductive layer is the outermost layer.
7. 10. The multi-layer material of claim 1, wherein the thermally conductive layer is in a form selected from the group consisting of a mesh, a sheet, a perforated sheet, a foil, and a perforated foil.
8. The multi-layer material of claim 1 , wherein the insulating layer comprises mica, ceramic, inorganic fiber cotton, resin, or inorganic foam.
9. The multi-layer material of claim 1 , wherein the insulating layer comprises an aerogel.
10. 10. The multi-layer material of claim 9, wherein the aerogel comprises a reinforcement material.
11. 11. The multi-layer material of claim 10, wherein the reinforcement material comprises fibers selected from organic polymer-based fibers, inorganic fibers, carbon-based fibers, or combinations thereof.
12. 12. The multi-layer material of claim 11, wherein the fibers are in the form of separate fibers, a woven material, a dry-laid nonwoven material, a wet-laid nonwoven material, a needle-punched nonwoven, a batting, a web, a mat, a felt, and / or combinations thereof.
13. 12. The multi-layer material of claim 11, wherein the inorganic fibers are selected from glass fibers, rock fibers, metal fibers, boron fibers, ceramic fibers, basalt fibers, or combinations thereof.
14. 10. The multi-layer material of claim 9, wherein the aerogel comprises a silica-based aerogel.
15. 10. The multi-layer material of claim 9, wherein the aerogel comprises one or more additives, the one or more additives being present in an amount of about 5 to 20 weight percent of the aerogel.
16. 16. The multi-layer material of claim 15, wherein the one or more additives are present in an amount of about 10 to 20 weight percent of the aerogel.
17. 16. The multi-layer material of claim 15, wherein the one or more additives comprises a fire-rated additive.
18. The one or more additives are 4 C, diatomaceous earth, manganese ferrite, MnO, NiO, SnO, Ag 2 O.B.I. 2 O 3 16. The multilayer material of claim 15, comprising an opacifying agent selected from TiC, WC, carbon black, titanium oxide, iron titanium oxide, zirconium silicate, zirconium oxide, iron (I) oxide, iron (III) oxide, manganese dioxide, iron titanium oxide (ilmenite), chromium oxide, or mixtures thereof.
19. 16. The multi-layer material of claim 15, wherein the one or more additives include an opacifier comprising silicon carbide.
20. 16. The multi-layer material of claim 15, wherein the one or more additives include a combination of a fire-rated additive and an opacifier.
21. 10. The multi-layer material of claim 9, wherein the aerogel has a density ranging from about 0.25 g / cc to about 1.0 g / cc when measured according to ASTM C167 standard at a compressive force of 2 psi.
22. 10. The multi-layer material of claim 9, wherein the aerogel has a flexural modulus of about 2 MPa to about 8 MPa as measured by a three-point bending test.
23. 10. The multi-layer material of claim 9, wherein the aerogel exhibits compression resistance, and the compression resistance at 25% strain is between about 40 kPa and about 180 kPa.
24. 10. The multilayer material of claim 1, further comprising a heat capacity layer disposed between a portion of the thermally conductive layer and the insulating layer, the heat capacity layer having a specific heat capacity of at least about 0.2 J / (g °C).
25. 25. The multi-layer material of claim 24, wherein the heat capacity layer comprises a phase change material.
26. 25. The multi-layer material of claim 24, wherein the heat capacity layer comprises a metal comprising aluminum, titanium, nickel, steel, or iron.
27. The multi-layer material of claim 1 , further comprising a sacrificial material layer disposed between a portion of the thermally conductive layer and the insulating layer.
28. 30. The multi-layer material of claim 27, wherein the sacrificial material layer comprises a material selected from the group consisting of siloxanes, polyolefins, polyurethanes, phenolics, melamines, cellulose acetates, and polystyrenes.
29. 30. The multi-layer material of claim 27, wherein the sacrificial material layer is in the form of a foam.
30. 28. The multi-layer material of claim 27, wherein the onset temperature of chemical decomposition of the sacrificial material layer ranges from about 200° C. to about 400° C. as measured using thermogravimetric analysis.
31. The multi-layer material of claim 1 , further comprising an encapsulation layer disposed between the thermally conductive layer and the insulating layer.
32. 32. The multi-layer material of claim 31 , wherein the encapsulant layer comprises one or more polymer layers.
33. The multi-layer material of claim 1 , wherein the multi-layer material has an average thickness in an uncompressed state of between about 2 mm and about 10 mm.
34. 34. The multilayer material of any one of claims 1 to 33, wherein the thermally conductive layer is substantially L-shaped, a vertical portion of the L-shaped thermally conductive layer being spaced apart from the insulating layer, a horizontal portion of the L-shaped thermally conductive layer being in contact with the insulating layer, and one or more of an encapsulating material layer, a sacrificial material layer, and a heat capacity layer being disposed between the vertical portion of the L-shaped thermally conductive layer and the insulating layer.
Citation Information
Patent Citations
Cushion material and method of manufacturing the same
JP2011244867A
Heat insulation material, heat generation unit using the same and battery unit
JP2018204708A
Heat insulation material, manufacturing method thereof, electronic apparatus using it, and automobile
JP2020060291A
Adiabatic sheet and its manufacturing method, as well as electronic apparatus and battery unit
JP2020193413A
Battery module
WO2019167612A1